In vitro growth inhibition and cytotoxicity of Euphorbia caducifolia against four human cancer cell lines and its phytochemical characterisation - Shaista Bano; Bina Shaheen Siddiqui; Ahsana Dar Farooq; Sabira Begum; Faheema Siddiqui; Muhammad Kashif; Mudassar Azhar (Natural Product Research, 2017)

Toward N-nitrosamines free water: Formation, prevention, and removal - Peter Adeniyi Alaba; Yahaya Muhammad Sani; Sunday Felix Olupinla; Wan Mohd Wan Daud; Isah Yakub Mohammed; Christopher C. Enweremadu; Olubunmi O. Ayodele (Critical Reviews in Environmental Science and Technology, 2017)

Comparison of Seasonal Cycles of Phytoplankton Chlorophyll, Aerosols, Winds and Sea-Surface Temperature off Somalia - Muhammad Shafeeque; Shubha Sathyendranath; Grinson George; Alungal N. Balchand; Trevor Platt (Frontiers in Marine Science, 2017)

Evaluating Korean rice genotypes and landraces for octacosanol contents and antioxidant activity - Yang-Hee Cho; Rozbeh Farhoudi; Muhammad Farooq; Dong-Jin Lee (Natural Product Research, 2017)

Advances and future directions of biochar characterization methods and applications - Avanthi Deshani Igalavithana; Sanchita Mandal; Nabeel Khan Niazi; Meththika Vithanage; Sanjai J. Parikh; Fungai N. D. Mukome; Muhammad Rizwan; Patryk Oleszczuk; Mohammad Al-Wabel; Nanthi Bolan; Daniel C. W. Tsang; Ki-Hyun Kim; et al. (Critical Reviews in Environmental Science and Technology, 2017)

A Novel Multi-Scalar Drought Index for Monitoring Drought: the Standardized Precipitation Temperature Index - Zuliqar Ali; Ijaz Hussain; Muhammad Faisal; Hafiza Mamona Nazir; Mitwali Abd-el Moemen; Tajammal Hussain; Sadaf Shamsuddin (Water Resources Management, 2017)

Role of circulatory microRNAs in the pathogenesis of hepatitis C virus - Iqra Almas; Samia Afzal; Muhammad Idrees; Muhammad Usman Ashraf; Iram Amin; Muhammad Shahid; Khadija Zahid; Sadia Zahid (VirusDisease, 2017)

Expression Profiles of Wuschel-Related Homeobox Gene Family in Pineapple (Ananas comosus L) - Zia ur Rahman; Syed Muhammad Azam; Yanhui Liu; Cheng Yan; Hina Ali; Lihua Zhao; Piaojuan Chen; Li Yi; S. V. G. N. Priyadarshani; Qin Yuan (Tropical Plant Biology, 2017)

Regenerative Potential of Platelet Rich Fibrin (PRF) for Curing Intrabony Periodontal Defects: A Systematic Review of Clinical Studies - Shariq Najeeb; Zohaib Khurshid; Muhammad Atif Saleem Agwan; Shazia Akhbar Ansari; Muhammad Sohail Zafar; Jukka Pekka Matinlinna (Tissue Engineering and Regenerative Medicine, 2017)

Agroforestry Systems as Alternative Land-Use Options in the Arid Zone of Thal, Pakistan - Muhammad Khan; Hafiz Zahid Mahmood; Ghulam Abbas; Christos A. Damalas (Small-scale Forestry, 2017)

Profile and Time-Scale Dynamics of Differentially Expressed Genes in Transcriptome of Populus davidiana Under Drought Stress - Bong-Gyu Mun; Adil Hussain; Eung-Jun Park; Sang-Uk Lee; Arti Sharma; Qari Muhammad Imran; Ki-Hong Jung; Byung-Wook Yun (Plant Molecular Biology Reporter, 2017)

New small mammals from the Hasnot–Tatrot area of the Potwar Plateau, northern Pakistan - Muhammad Akbar Khan; Lawrence J. Flynn (PalZ, 2017)

Ag-loaded thermo-sensitive composite microgels for enhanced catalytic reduction of methylene blue - Luqman Ali Shah; Murtaza Sayed; Muhammad Fayaz; Irum Bibi; Mohsan Nawaz; Mohammad Siddiq (Nanotechnology for Environmental Engineering, 2017)

Evaluating the variability and trends in extreme climate events in the Kashmir Valley using PRECIS RCM simulations - Ishfaq Gujree; Ishfaq Wani; Muhammad Muslim; Majid Farooq; Gowhar Meraj (Modeling Earth Systems and Environment, 2017)

Suppression of PGE2 production via disruption of MAPK phosphorylation by unsymmetrical dicarbonyl curcumin derivatives - Mohd Fadhlizil Fasihi Mohd Aluwi; Kamal Rullah; Md. Areeful Haque; Bohari M. Yamin; Waqas Ahmad; Muhammad Wahab Amjad; Sze Wei Leong; Nurul Amira Fahmizar; Juriyati Jalil; Faridah Abas; Nor Hadiani Ismail; Ibrahim Jantan; et al. (Medicinal Chemistry Research, 2017)

Molecular docking and glucosidase inhibition studies of novel N-arylthiazole-2-amines and Ethyl 2-[aryl(thiazol-2-yl)amino]acetates - Ayesha Babar; Muhammad Yar; Hamadeh Tarazi; Vera Duarte; Mohammed B. Alshammari; Mazhar Amjad Gilani; Haffsah Iqbal; Munawwar Ali Munawwar; Maria J. Alves; Ather Farooq Khan (Medicinal Chemistry Research, 2017)

Anti-epileptic activity of Nelumbo nucifera fruit - Muhammad Ali Rajput; Rafeeq Alam Khan; Tahira Assad (Metabolic Brain Disease, 2017)

Decreased brain serotonin turnover rate following administration of Sharbat-e-Ahmed Shah produces antidepressant and anxiolytic effect in rats - Muhammad Ahmed; Aisha Azmat (Metabolic Brain Disease, 2017)

Combined Applications of Aminoethoxyvinylglycine with Salicylic Acid or Nitric Oxide Reduce Oxidative Stress in Peach During Ripening and Cold Storage - Mohammad Javed Tareen; Zora Singh; Ahmad Sattar Khan; Nadeem Akhtar Abbasi; Muhammad Naveed (Journal of Plant Growth Regulation, 2017)

Assessment of resistance to bacterial wilt incited by Ralstonia solanacearum in tomato germplasm - Muhammad Naveed Aslam; Tariq Mukhtar; Muhammad Arshad Hussain; Muhammad Raheel (Journal of Plant Diseases and Protection, 2017)

Coral recruitment success and sessile benthic colonisation estimation in Tioman Island Marine Park, Malaysia - M. H. Muhammad Faiz; S. Shahbudin; Yukinori Mukai (Journal of Coastal Conservation, 2017)

On the ratio of intercellular to ambient CO2 (c i/c a) derived from ecosystem flux - Zheng-Hong Tan; Zhi-Xiang Wu; Alice C. Hughes; Douglas Schaefer; Jiye Zeng; Guo-Yu Lan; Chuang Yang; Zhong-Liang Tao; Bang-Qian Chen; Yao-Hua Tian; Liang Song; Muhammad Tahir Jatoi; et al. (International Journal of Biometeorology, 2017)

Sympatric snow leopards and Tibetan wolves: coexistence of large carnivores with human-driven potential competition - Anna Bocci; Sandro Lovari; Muhammad Zafar Khan; Emiliano Mori (European Journal of Wildlife Research, 2017)

Potentially Toxic Metals and Biological Contamination in Drinking Water Sources in Chromite Mining-Impacted Areas of Pakistan: A Comparative Study - Javed Nawab; Sardar Khan; Muhammad Amjad Khan; Hassan Sher; Ubaid Ur Rehamn; Sharafat Ali; Syed Mehboob Shah (Exposure and Health, 2017)

Excessive use of nitrogenous fertilizers: an unawareness causing serious threats to environment and human health - Moddassir Ahmed; Muhammad Rauf; Zahid Mukhtar; Nasir Ahmad Saeed (Environmental Science and Pollution Research, 2017)

3D graphene-based nanostructured materials as sorbents for cleaning oil spills and for the removal of dyes and miscellaneous pollutants present in water - Muhammad Adil Riaz; Gordon McKay; Junaid Saleem (Environmental Science and Pollution Research, 2017)

Influence of entomopathogenic fungus, Metarhizium anisopliae, alone and in combination with diatomaceous earth and thiamethoxam on mortality, progeny production, mycosis, and sporulation of the stored grain insect pests - Misbah Ashraf; Muhammad Farooq; Muhammad Shakeel; Naima Din; Shahbaz Hussain; Nadia Saeed; Qaiser Shakeel; Nasir Ahmed Rajput (Environmental Science and Pollution Research, 2017)

Seasonal variation of heavy metals in water and sediments in the Halda River, Chittagong, Bangladesh - Md. Simul Bhuyan; Muhammad Abu Bakar (Environmental Science and Pollution Research, 2017)

Growth promoting potential of fresh and stored Moringa oleifera leaf extracts in improving seedling vigor, growth and productivity of wheat crop - Shahbaz Khan; Shahzad Maqsood Ahmed Basra; Irfan Afzal; Muhammad Nawaz; Hafeez Ur Rehman (Environmental Science and Pollution Research, 2017)

Evaluating the health risks of potentially toxic elements through wheat consumption in multi-industrial metropolis of Faisalabad, Pakistan - Qumber Abbas; Balal Yousaf; Guijian Liu; Muhammad Zia-ur-Rehman; Muhammad Ubaid Ali; Mehr Ahmed Mujtaba Munir; Syed Arif Hussain (Environmental Science and Pollution Research, 2017)

Impact of socio-demographic factors on the mitigating actions for climate change: a path analysis with mediating effects of attitudinal variables - Muhammad Mehedi Masud; Rulia Akhatr; Shamima Nasrin; Ibrahim Mohammed Adamu (Environmental Science and Pollution Research, 2017)

Determining soil quality in urban agricultural regions by soil enzyme-based index - Avanthi Deshani Igalavithana; Muhammad Farooq; Kye-Hoon Kim; Young-Han Lee; Muhammad Farooq Qayyum; Mohammad I. Al-Wabel; Sang Soo Lee; Yong Sik Ok (Environmental Geochemistry and Health, 2017)

Multi-metal resistance and plant growth promotion potential of a wastewater bacterium Pseudomonas aeruginosa and its synergistic benefits - Jayanta Kumar Biswas; Monojit Mondal; Jörg Rinklebe; Santosh Kumar Sarkar; Punarbasu Chaudhuri; Mahendra Rai; Sabry M. Shaheen; Hocheol Song; Muhammad Rizwan (Environmental Geochemistry and Health, 2017)

Mucilaginibacter ginsenosidivorans sp. nov., Isolated from Soil of Ginseng Field - Minseok M. Kim; Muhammad Zubair Siddiqi; Wan-Taek Im (Current Microbiology, 2017)

Thiolation of arabinoxylan and its application in the fabrication of controlled release mucoadhesive oral films - Muhammad Hanif; Muhammad Zaman (DARU Journal of Pharmaceutical Sciences, 2017)

Quantitative interpretation of carbonate reservoir rock using wireline logs: a case study from Central Luconia, offshore Sarawak, Malaysia - Hammad Tariq Janjuhah; Ahmed Mohammad Ahmed Salim; Mumtaz Muhammad Shah; Deva Ghosh; Abubaker Alansari (Carbonates and Evaporites, 2017)

Regenerative Stem Cell Therapy Optimization via Tissue Engineering in Heart Failure with Reduced Ejection Fraction - Mehmet Alkan; Raef Madanieh; Niel N. Shah; Muhammad U. Dogar; Parin N. Shah; Sameera Ishtiaq; Constantine E. Kosmas; Timothy J. Vittorio (Cardiovascular Engineering and Technology, 2017)

Basic leucine zipper domain transcription factors: the vanguards in plant immunity - Ali Noman; Zhiqin Liu; Muhammad Aqeel; Madiha Zainab; Muhammad Ifnan Khan; Ansar Hussain; Muhammad Furqan Ashraf; Xia Li; Yahong Weng; Shuilin He (Biotechnology Letters, 2017)

Assessment of sea water inundation along Daboo creek area in Indus Delta Region, Pakistan - Ibrahim Zia; Hina Zafar; Muhammad I. Shahzad; Mohsin Meraj; Jamil H. Kazmi (Journal of Ocean University of China, 2017)

Ellis–van Creveld syndrome and profound deafness resulted by sequence variants in the EVC / EVC2 and TMC1 genes - Muhammad Umair; Heide Seidel; Ishtiaq Ahmed; Asmat Ullah; Tobias B. Haack; Bader Alhaddad; Abid Jan; Afzal Rafique; Tim M. Strom; Farooq Ahmad; Thomas Meitinger; Wasim Ahmad (Journal of Genetics, 2017)

Erratum to: Experimental investigation of immiscible supercritical carbon dioxide foam rheology for improved oil recovery - Shehzad Ahmed; Khaled Abdalla Elraies; Jalal Foroozesh; Siti Rohaida Bt Mohd Shafian; Muhammad Rehan Hashmet; Ivy Chai Ching Hsia; Abdullah Almansour (Journal of Earth Science, 2017)

A novel homozygous frameshift variant in the MCPH1 gene causes primary microcephaly in a consanguineous Saudi family - Muhammad Imran Naseer; Mahmood Rasool; Osama Yousef Muthaffar; Abdulrahman J. Sabbagh; Adeel G. Chaudhary; Mohammad H. Al-Qahtani (Genes & Genomics, 2017)

Genetic Testing of Non-familial Deaf Patients for CIB2 and GJB2 Mutations: Phenotype and Genetic Counselling - Hina Shaikh; Ali M. Waryah; Ashok K. Narsani; Muhammad Iqbal; Mohsin Shahzad; Yar M. Waryah; Naila Shaikh; Amber Mahmood (Biochemical Genetics, 2017)

A measles outbreak in Sindh, Pakistan caused by a genotype B3 virus - Syed Sohail Zahoor Zaidi; Abdul Hameed; Naeem Ali; Massab Umair; Muhammad Masroor Alam; Muhammad Suleman Rana; Salmaan Sharif; Uzma Bashir Aamir; Shahzad Shaukat; Mehar Angez; Adnan Khurshid; Ribqa Akhtar; et al. (Archives of Virology, 2017)

Detection of Verticillium species in Swedish soils using real-time PCR - Georgios Tzelepis; Sarosh Bejai; Muhammad Naeem Sattar; Arne Schwelm; Jonas Ilbäck; Johan Fogelqvist; Christina Dixelius (Archives of Microbiology, 2017)

Evaluating groundwater quality for irrigated agriculture: spatio-temporal investigations using GIS and geostatistics in Punjab, Pakistan - Muhammad Awais; Muhammad Arshad; Syed Hamid Hussain Shah; Muhammad Anwar-ul-Haq (Arabian Journal of Geosciences, 2017)

Petrography, provenance, diaganesis and depositional environment of Murree Formation in Jhelum Valley, Sub Himalayas, Azad Jammu and Kashmir, Pakistan - Muhammad Zaheer; Muhammad Sabir Khan; Muhammad Saleem Mughal; Noman Abbasi (Arabian Journal of Geosciences, 2017)

Rice bran nutraceutics: A comprehensive review - Muhammad Sohail; Allah Rakha; Masood Sadiq Butt; Muhammad Jawad Iqbal; Summer Rashid (Critical Reviews in Food Science and Nutrition, 2017)

Evaluation of Green Waste and Popular Twigs Biochar Produced at Low and High Pyrolytic Temperature for Efficient Removal of Metals from Water - Zeshan Aslam; Muhammad Khalid; Muhammad Naveed; Muhammad Shahid; Muhammad Aon (Water, Air, & Soil Pollution, 2017)

Artificial Neural Network (ANN) for Modelling Adsorption of Lead (Pb (II)) from Aqueous Solution - Taimur Khan; Muhammad Raza Ul Mustafa; Mohamed Hasnain Isa; Teh Sabariah Binti Abd Manan; Yeek-Chia Ho; Jun-Wei Lim; Nur Zulaikha Yusof (Water, Air, & Soil Pollution, 2017)

Singular value decomposition analysis for examining the impact of Siberian High on winter precipitation variability over South Asia - Syed Muhammad Fahad Riaz; Muhammad Jawed Iqbal (Theoretical and Applied Climatology, 2017)

Nitrogen-regulated changes in total amino acid profile of maize genotypes having contrasting response to nitrogen deficit - Arshid Hussain Ganie; Altaf Ahmad; Peerzada Yasir Yousuf; Renu Pandey; Sayeed Ahmad; Ibrahim M Aref; Muhammad Iqbal (Protoplasma, 2017)

Volatile terpenoids: multiple functions, biosynthesis, modulation and manipulation by genetic engineering - Farhat Abbas; Yanguo Ke; Rangcai Yu; Yuechong Yue; Sikandar Amanullah; Muhammad Muzammil Jahangir; Yanping Fan (Planta, 2017)

From REDD+ MRV Perspective: Comparison of Two Different Forest Management Regimes Using Geospatial Techniques in Ludi Khola Watershed, Gorkha District, Nepal - Hammad Gilani; Muhammad Sohail; Upama Ashish Koju (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2017)

Seasonality in hospital admissions of Crimean-Congo hemorrhagic fever and its dependence on ambient temperature—empirical evidence from Pakistan - Tariq Abbas; Zhiwei Xu; Muhammad Younus; Abdul Qayyum; Muhammad T. Riaz (International Journal of Biometeorology, 2017)

Pseudomonas syringae pv. tomato DC3000 growth in multiple gene knockouts predicts interactions among hormonal, biotic and abiotic stress responses - Muhammad Saleem; Hao Ji; Amalina Amirullah; Milton Brian Traw (European Journal of Plant Pathology, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Erratum to: Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Effects of co-composting of farm manure and biochar on plant growth and carbon mineralization in an alkaline soil - Muhammad Farooq Qayyum; Fatima Liaquat; Rabia Abdur Rehman; Mehreen Gul; Muhammad Zafar ul Hye; Muhammad Rizwan; Muhammad Zia ur Rehaman (Environmental Science and Pollution Research, 2017)

Economic assessment of conventional and conservation tillage practices in different wheat-based cropping systems of Punjab, Pakistan - Muhammad Shahzad; Mubshar Hussain; Muhammad Farooq; Shahid Farooq; Khawar Jabran; Ahmad Nawaz (Environmental Science and Pollution Research, 2017)

Phosphate-arsenate relations to affect arsenic concentration in plant tissues, growth, and antioxidant efficiency of sunflower (Helianthus annuus L.) under arsenic stress - Waqas Azeem; Muhammad Ashraf; Sher Muhammad Shahzad; Muhammad Imtiaz; Mumtaz Akhtar; Muhammad Shahid Rizwan (Environmental Science and Pollution Research, 2017)

Sub-chronic exposure to low concentration of dibutyl phthalate affects anthropometric parameters and markers of obesity in rats - Khalid Abdul Majeed; Habib ur Rehman; Muhammad Shahbaz Yousaf; Hafsa Zaneb; Imtiaz Rabbani; Sajid Khan Tahir; Muhammad Afzal Rashid (Environmental Science and Pollution Research, 2017)

Heavy metal phytoextraction—natural and EDTA-assisted remediation of contaminated calcareous soils by sorghum and oat - Muhammad Mahmood-ul-Hassan; Vishandas Suthar; Rizwan Ahmad; Munazza Yousra (Environmental Monitoring and Assessment, 2017)

Exploring standardized precipitation evapotranspiration index for drought assessment in Bangladesh - Md Giashuddin Miah; Hasan Muhammad Abdullah; Changyoon Jeong (Environmental Monitoring and Assessment, 2017)

Effects of effluent water on the abundance of cowpea insect pests - Bamphitlhi Tiroesele; Monametsi Sitwane; M. Obopile; Muhammad Irfan Ullah; Sajjad Ali (Environmental Monitoring and Assessment, 2017)

Assessing the combined toxicity of conventional and newer insecticides on the cotton mealybug Phenacoccus solenopsis - Bushra Saddiq; Masood Ejaz; Sarfraz Ali Shad; Muhammad Aslam (Ecotoxicology, 2017)

Contrasting Effects of Organic and Inorganic Amendments on Reducing Lead Toxicity in Wheat - Muhammad Zia ur Rehman; Muhammad Rizwan; Shafaqat Ali; Muhammad Sabir; Muhammad I. Sohail (Bulletin of Environmental Contamination and Toxicology, 2017)

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Pcal_1311, an alcohol dehydrogenase homologue from Pyrobaculum calidifontis, displays NADH-dependent high aldehyde reductase activity - Raza Ashraf; Naeem Rashid; Tamotsu Kanai; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Sensitivity of AGCM ‐simulated regional JJAS precipitation to different convective parameterization schemes - Muhammad Azhar Ehsan; Mansour Almazroui; Ahmed Yousef; O'Brien Enda; Michael K. Tippett; Fred Kucharski; Abdulrahman A. Alkhalaf (International Journal of Climatology, 2017)
This study examines the effects of convective parameterization schemes ( CPSs ) on the simulated June–September ( JJAS ) precipitation climatology, variability and predictability over southwestern Arabian Peninsula and northeast Africa during 1981–2014 within an atmospheric global climate model framework. The three CPSs used are: the simplified Arakawa–Schubert ( SAS ) scheme; the SAS scheme with Tokioka modification ( STOK ) and the Emanuel ( EMAN ) scheme coupled with a probability distribution function‐based cloud parameterization scheme. SAS and STOK overestimate JJAS total precipitation over the selected domain compared to observations, while EMAN underestimates. EMAN provides the most realistic distribution of precipitation and spatial distribution of convective precipitation despite the tendency for underestimating the total precipitation. The principal patterns of precipitation variability (as measured by the leading empirical orthogonal functions) in EMAN and STOK are clearly related to the observed pattern, while the maximum variability in SAS occurs in a completely different location. The El Niño Southern Oscillation‐related JJAS precipitation teleconnection simulated by the SAS scheme is very weak as compared to observations and other two CPSs . The signal‐to‐noise ratio estimated by SAS and STOK is very low as compared to EMAN . Correlation analysis shows that EMAN performs better than the other two CPSs . Low (high) outgoing longwave radiation ( OLR ) values are indicative of enhanced (suppressed) convection and hence more (less) cloud coverage. The root mean square error estimated for OLR in EMAN is lower than that of the other two CPSs . The vertical structure of specific humidity and temperature shows less error in EMAN than that of the other two CPSs , which could be a reason for better predictability over the region of interest.

Genes responsible for powdery mildew resistance and improvement in wheat using molecular marker-assisted selection - Liaqat Shah; Shamsur Rehman; Asif Ali; Muhammad Yahya; Muhammad Waheed Riaz; Hongqi Si; Chuanxi Ma; Jie Lu (Journal of Plant Diseases and Protection, 2017)

Engineering Pseudomonas for phenazine biosynthesis, regulation, and biotechnological applications: a review - Muhammad Bilal; Shuqi Guo; Hafiz M. N. Iqbal; Hongbo Hu; Wei Wang; Xuehong Zhang (World Journal of Microbiology and Biotechnology, 2017)

Effective Bioremediation of Endocrine-Disrupting Phthalate Esters, Mediated by Bacillus Strains - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Farah Amin; Abid Ali Khaskheli; Shazia Bhurgri; Hassan Imran Afridi; Shafiq Ur Rahman (Water, Air, & Soil Pollution, 2017)

Synthesis, Characterization, and Use of Carbon Microspheres for Removal of Different Dyes from Aqueous Environments - Nurettin Sahiner; Muhammad Farooq; Saif ur Rehman; Selin Sagbas; Mehtap Sahiner; Mohammad Siddiq; Nahit Aktas (Water, Air, & Soil Pollution, 2017)

Assessment of AquaCrop Model in Simulating Sugar Beet Canopy Cover, Biomass and Root Yield under Different Irrigation and Field Management Practices in Semi-Arid Regions of Pakistan - Abdul Malik; Abdul Sattar Shakir; Muhammad Ajmal; Muhammad Jamal Khan; Taj Ali Khan (Water Resources Management, 2017)

Reconsidering betaine as a natural anti-heat stress agent in poultry industry: a review - Muhammad Saeed; Daryoush Babazadeh; Muhammad Naveed; Muhammad Asif Arain; Faiz Ul Hassan; Sun Chao (Tropical Animal Health and Production, 2017)

Effect of a bradykinin-potentiating factor isolated from scorpion venom (Leiurus quinquestriatus) on some blood indices and lipid profile in irradiated rats - Muhammad M. A. Salman; Ahmed M. Kotb; Mohie A. M. Haridy; Klaus Golka; Seddik Hammad (Molecular and Cellular Biochemistry, 2017)

Synthesis, crystal structure, anti-HIV, and antiproliferative activity of new pyrazolylthiazole derivatives - Murtaza Madni; Shahid Hameed; Muhammad N. Ahmed; Muhammad N. Tahir; Najim A. Al-Masoudi; Christophe Pannecouque (Medicinal Chemistry Research, 2017)

Spatiotemporal patterns of correlation between atmospheric nitrogen dioxide and aerosols over South Asia - Zia ul-Haq; Salman Tariq; Muhammad Ali (Meteorology and Atmospheric Physics, 2017)

Detection of water infiltration and deformation of unsaturated soils by elastic wave velocity - Yulong Chen; Taro Uchimura; Muhammad Irfan; Dong Huang; Jiren Xie (Landslides, 2017)

Photocatalytic Degradation of Pentachlorophenol Using ZnO Nanoparticles: Study of Intermediates and Toxicity - Muneer M. Ba-Abbad; Mohd S. Takriff; Muhammad Said; Abdelbaki Benamor; Mustafa S. Nasser; Abdul Wahab Mohammad (International Journal of Environmental Research, 2017)

In vitro regeneration of Abelmoschus esculentus L. cv. Wufu: Influence of anti-browning additives on phenolic secretion and callus formation frequency in explants - Muhammad Irshad; Bizhu He; Shuang Liu; Sangeeta Mitra; Biswojit Debnath; Min Li; Hafiz Muhammad Rizwan; Dongliang Qiu (Horticulture, Environment, and Biotechnology, 2017)

Recent advances in assessment on clear water, soil and air - Muhammad Aqeel Ashraf; Marlia Mohd Hanfiah (Environmental Science and Pollution Research, 2017)

Nitrogen nutrition in cotton and control strategies for greenhouse gas emissions: a review - Aziz Khan; Daniel Kean Yuen Tan; Fazal Munsif; Muhammad Zahir Afridi; Farooq Shah; Fan Wei; Shah Fahad; Ruiyang Zhou (Environmental Science and Pollution Research, 2017)

PTFE-coated non-stick cookware and toxicity concerns: a perspective - Muhammad Sajid; Muhammad Ilyas (Environmental Science and Pollution Research, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Marble industry effluents cause an increased bioaccumulation of heavy metals in Mahaseer (Tor putitora) in Barandu River, district Buner, Pakistan - Shahi Mulk; Abdul Latif Korai; Azizullah Azizullah; Lubna Shahi; Muhammad Nasir Khan Khattak (Environmental Science and Pollution Research, 2017)

The fate and transport of arsenic species in the aquatic ecosystem: a case study on Bestari Jaya, Peninsular Malaysia - Suzanne Christine Aboudi Mana; Ng Tham Fatt; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Chemical speciation and bioavailability of rare earth elements (REEs) in the ecosystem: a review - Aysha Masood Khan; Nor Kartini Abu Bakar; Ahmad Farid Abu Bakar; Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Correlation of lithium levels between drinking water obtained from different sources and scalp hair samples of adult male subjects - Shahnawaz Baloch; Tasneem Gul Kazi; Hassan Imran Afridi; Jameel Ahmed Baig; Farah Naz Talpur; Muhammad Balal Arain (Environmental Geochemistry and Health, 2017)

The Potential Use of Vetiveria zizanioides for the Phytoremediation of Antimony, Arsenic and Their Co-Contamination - Nosheen Mirza; Hussani Mubarak; Li-Yuan Chai; Wang Yong; Muhammad Jamil Khan; Qudrat Ullah Khan; Muhammad Zaffar Hashmi; Umar Farooq; Rizwana Sarwar; Zhi-Hui Yang (Bulletin of Environmental Contamination and Toxicology, 2017)

Proteomic approach to address low seed germination in Cyclobalnopsis gilva - Madiha Zaynab; Sonia Kanwal; Muhammad Furqan; Waqar Islam; Ali Noman; Ghulam Muhammad Ali; Nazia Rehman; Sara Zafar; Kalsoom Sughra; Muhammad Jahanzab (Biotechnology Letters, 2017)

Targeted expression of insecticidal hybrid SN19 gene in potato leads to enhanced resistance against Colorado potato beetle (Leptinotarsa decemlineata Say) and tomato leafminer (Tuta absoluta Meyrick) - Hussein Abdullah Ahmed Ahmed; Selma Onarıcı; Allah Bakhsh; Güray Akdoğan; Ömer Cem Karakoç; Sancar Fatih Özcan; Gülsüm Aydın; Muhammad Aasım; Levent Ünlü; Cengiz Sancak; Samir Naimov; Sebahattin Özcan (Plant Biotechnology Reports, 2017)

Mapping the change of coral reefs using remote sensing and in situ measurements: a case study in Pangkajene and Kepulauan Regency, Spermonde Archipelago, Indonesia - La Ode Muhammad Yasir Haya; Masahiko Fujii (Journal of Oceanography, 2017)

Using Landsat images to monitor changes in the snow-covered area of selected glaciers in northern Pakistan - Chaman Gul; Shi-chang Kang; Badar Ghauri; Mateeul Haq; Sher Muhammad; Shaukat Ali (Journal of Mountain Science, 2017)

Experimental investigation of immiscible supercritical carbon dioxide foam rheology for improved oil recovery - Shehzad Ahmed; Khaled Abdalla Elraies; Jalal Forooozesh; Siti Rohaida Bt Mohd Shafian; Muhammad Rehan Hashmet; Ivy Chai Ching Hsia; Abdullah Almansour (Journal of Earth Science, 2017)

An application of variogram modelling for electrical resistivity soundings to characterize depositional system and hydrogeology of Bannu Basin, Pakistan - Asam Farid; Perveiz Khalid; Khan Zaib Jadoon; Muhammad Asim Iqbal; James Small (Geosciences Journal, 2017)

Assessment of heavy metals concentration in phosphate rock deposits, Hazara basin, Lesser Himalaya Pakistan - Faridullah Faridullah; Muhammad Umar; Arif Alam; Muhammad Amjad Sabir; Danyal Khan (Geosciences Journal, 2017)

Identification of novel potential genetic predictors of urothelial bladder carcinoma susceptibility in Pakistani population - Syeda Hafiza Benish Ali; Kashif Sardar Bangash; Abdur Rauf; Muhammad Younis; Khursheed Anwar; Raja Khurram; Muhammad Athar Khawaja; Maleeha Azam; Abid Ali Qureshi; Saeed Akhter; Lambertus A. Kiemeney; Raheel Qamar (Familial Cancer, 2017)

Differential effects of plant growth regulators on physiology, steviol glycosides content, and antioxidant capacity in micropropagated tissues of Stevia rebaudiana - Rabia Javed; Buhara Yucesan; Muhammad Zia; Ekrem Gurel (Biologia, 2017)

Bioherbicidal activity of allelopathic bacteria against weeds associated with wheat and their effects on growth of wheat under axenic conditions - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed (BioControl, 2017)

Evolutionary insights into the fusion protein of Newcastle disease virus isolated from vaccinated chickens in 2016 in Egypt - Ahmed Orabi; Ashraf Hussein; Ayman A. Saleh; Mohammed Abu El-Magd; Muhammad Munir (Archives of Virology, 2017)

Modulation of Wnt signaling pathway by hepatitis B virus - Muhammad Daud; Muhammad Adeel Rana; Tayyab Husnain; Bushra Ijaz (Archives of Virology, 2017)

Using geographical information systems to assess groundwater contamination from arsenic and related diseases based on survey data in Lahore, Pakistan - Muhammad Imran; Sohail Jahanzaib; Ather Ashraf (Arabian Journal of Geosciences, 2017)

Seismic activity prediction using computational intelligence techniques in northern Pakistan - Khawaja M. Asim; Muhammad Awais; F. Martínez–Álvarez; Talat Iqbal (Acta Geophysica, 2017)

DHI evaluation by combining rock physics simulation and statistical techniques for fluid identification of Cambrian-to-Cretaceous clastic reservoirs in Pakistan - Nisar Ahmed; Perveiz Khalid; Hafiz Muhammad Bilal Shafi; Patrick Connolly (Acta Geophysica, 2017)

Unravelling proximate cues of mass flowering in the tropical forests of South‐East Asia from gene expression analyses - Suat Hui Yeoh; Akiko Satake; Shinya Numata; Tomoaki Ichie; Soon Leong Lee; Norlia Basherudin; Norwati Muhammad; Toshiaki Kondo; Tatsuya Otani; Mazlan Hashim; Naoki Tani (Molecular Ecology, 2017)
Elucidating the physiological mechanisms of the irregular yet concerted flowering rhythm of mass flowering tree species in the tropics requires long‐term monitoring of flowering phenology, exogenous and endogenous environmental factors, as well as identifying interactions and dependencies among these factors. To investigate the proximate factors for floral initiation of mast seeding trees in the tropics, we monitored the expression dynamics of two key flowering genes, meteorological conditions and endogenous resources over two flowering events of Shorea curtisii and Shorea leprosula in the Malay Peninsula. Comparisons of expression dynamics of genes studied indicated functional conservation of FLOWERING LOCUS T ( FT ) and LEAFY ( LFY ) in Shorea . The genes were highly expressed at least 1 month before anthesis for both species. A mathematical model considering the synergistic effect of cool temperature and drought on activation of the flowering gene was successful in predicting the observed gene expression patterns. Requirement of both cool temperature and drought for floral transition suggested by the model implies that flowering phenologies of these species are sensitive to climate change. Our molecular phenology approach in the tropics sheds light on the conserved role of flowering genes in plants inhabiting different climate zones and can be widely applied to dissect the flowering processes in other plant species.

Groundwater status in Pakistan: A review of contamination, health risks, and potential needs - Maimoona Raza; Fida Hussain; Jin-Yong Lee; Muhammad Bilal Shakoor; Kideok D. Kwon (Critical Reviews in Environmental Science and Technology, 2017)

Effect of Fixed Media Surface Area on Biofouling and Nutrients Removal in Fixed Film Membrane Bioreactor Treating Sewage at Medium and High Fluxes - Muhammad Zeeshan; Sajjad Haydar; Shamas Tabraiz (Water, Air, & Soil Pollution, 2017)

Flexible Alumina-Silica Nanofibrous Membrane and Its High Adaptability in Reactive Red-120 Dye Removal from Water - Muhammad Zobayer Bin Mukhlish; Yuji Horie; Teruaki Nomiyama (Water, Air, & Soil Pollution, 2017)

Projected Changes of Future Extreme Drought Events under Numerous Drought Indices in the Heilongjiang Province of China - Muhammad Imran Khan; Dong Liu; Qiang Fu; Qaisar Saddique; Muhammad Abrar Faiz; Tianxiao Li; Muhammad Uzair Qamar; Song Cui; Chen Cheng (Water Resources Management, 2017)

A Multiscale Approach to Leak Detection and Localization in Water Pipeline Network - Najam us Saqib; Muhammad Faizan Mysorewala; Lahouari Cheded (Water Resources Management, 2017)

Genome-Wide Identification of Auxin Response Factor (ARF) Genes Family and its Tissue-Specific Prominent Expression in Pineapple (Ananas comosus) - Zhenxia Su; Lulu Wang; Weimin Li; Lihua Zhao; Xinyu Huang; Syed Muhammad Azam; Yuan Qin (Tropical Plant Biology, 2017)

Pre-drought priming sustains grain development under post-anthesis drought stress by regulating the growth hormones in winter wheat (Triticum aestivum L.) - Muhammad Abid; Yuhang Shao; Sixi Liu; Feng Wang; Jingwen Gao; Dong Jiang; Zhongwei Tian; Tingbo Dai (Planta, 2017)

Statistical methodology for biosorption of nitrate (NO3 −) ions from aqueous solution by Pleurotus eryngii fungal biomass - Farah Amin; Farah Naz Talpur; Aamna Balouch; Hassan Imran Afridi; Muhammad Ali Surhio (Modeling Earth Systems and Environment, 2017)

Metachromatic Leukodystrophy (MLD): a Pakistani Family with Novel ARSA Gene Mutation - Muhammad Aiman Shahzad; Saba Khaliq; Ali Amar; Saqib Mahmood (Journal of Molecular Neuroscience, 2017)

Erratum to: Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater-A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; S. I. Mustapha; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Recent developments in immobilizing titanium dioxide on supports for degradation of organic pollutants in wastewater- A review - M. H. Alhaji; K. Sanaullah; A. Khan; A. Hamza; A. Muhammad; M. S. Ishola; A. R. H. Rigit; S. A. Bhawani (International Journal of Environmental Science and Technology, 2017)

Postpartum endocrine activities, metabolic attributes and milk yield are influenced by thermal stress in crossbred dairy cows - Ihsanullah; Muhammad Subhan Qureshi; Syed Muhammad Suhail; Sohail Akhtar; Rifat Ullah Khan (International Journal of Biometeorology, 2017)

Essential oils of aromatic Egyptian plants repel nymphs of the tick Ixodes ricinus (Acari: Ixodidae) - Hesham R. El-Seedi; Muhammad Azeem; Nasr S. Khalil; Hanem H. Sakr; Shaden A. M. Khalifa; Khalijah Awang; Aamer Saeed; Mohamed A. Farag; Mohamed F. AlAjmi; Katinka Pålsson; Anna-Karin Borg-Karlson (Experimental and Applied Acarology, 2017)

Molecular and biologic characterization of a phytoplasma associated with Brassica campestris phyllody disease in Punjab province, Pakistan - Jam Nazeer Ahmad; Samina J. N. Ahmad; Muhammad Aslam; Muhammad Aijaz Ahmad; Nicoletta Contaldo; Samanta Paltrinieri; Assunta Bertaccini (European Journal of Plant Pathology, 2017)

Biochar increased photosynthetic and accessory pigments in tomato (Solanum lycopersicum L.) plants by reducing cadmium concentration under various irrigation waters - Muhammad Abid; Subhan Danish; Muhammad Zafar-ul-Hye; Muhammad Shaaban; Muhammad Mutahir Iqbal; Abdur Rehim; Muhammad Farooq Qayyum; Muhammad Nadir Naqqash (Environmental Science and Pollution Research, 2017)

Foliar application of aspartic acid lowers cadmium uptake and Cd-induced oxidative stress in rice under Cd stress - Muhammad Rizwan; Shafaqat Ali; Muhammad Zaheer Akbar; Muhammad Bilal Shakoor; Abid Mahmood; Wajid Ishaque; Afzal Hussain (Environmental Science and Pollution Research, 2017)

Synthesis of piperazine functionalized magnetic sporopollenin: a new organic-inorganic hybrid material for the removal of lead(II) and arsenic(III) from aqueous solution - Naqhiyah Farhan Ahmad; Muhammad Afzal Kamboh; Hamid Rashidi Nodeh; Siti Nadiah Binti Abd Halim; Sharifah Mohamad (Environmental Science and Pollution Research, 2017)

Wheat productivity responses in the rice-based system under different no-till techniques and nitrogen sources - Muhammad Hamid Rafiq; Riaz Ahmad; Abdul Jabbar; Hassan Munir; Muzzammil Hussain (Environmental Science and Pollution Research, 2017)

The effect of corn distiller’s dried grains with solubles (DDGS) fortified with enzyme on growth performance of broiler - Alaeldein Mahmood Abudabos; Raed Muhammad Al-Atiyat; Dragons Stanley; Rafat Aljassim; Hamad Ali Albatshan (Environmental Science and Pollution Research, 2017)

Pb-induced changes in roots of two cultivated rice cultivars grown in lead-contaminated soil mediated by smoke - Nazneen Akhtar; Sehresh Khan; Ijaz Malook; Shafiq Ur Rehman; Muhammad Jamil (Environmental Science and Pollution Research, 2017)

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress - Mujahid Farid; Shafaqat Ali; Muhammad Rizwan; Rashid Saeed; Hafiz Muhammad Tauqeer; Rasham Sallah-Ud-Din; Ahmed Azam; Nighat Raza (Environmental Science and Pollution Research, 2017)

Nickel stressed responses of rice in Ni subcellular distribution, antioxidant production, and osmolyte accumulation - Muhammad Rizwan; Muhammad Imtiaz; Zhihua Dai; Sajid Mehmood; Muhammad Adeel; Jinchang Liu; Shuxin Tu (Environmental Science and Pollution Research, 2017)

Comparison of dynamic behaviours of retrofitted and unretrofitted cob material walls - Muhammad Masood Rafi; Sarosh Hashmat Lodi (Bulletin of Earthquake Engineering, 2017)

Robust approach for optimal positioning and ranking potential rainwater harvesting structure (RWH): a case study of Iraq - Khamis Naba Sayl; Nur Shazwani Muhammad; Ahmed El-Shafie (Arabian Journal of Geosciences, 2017)

Satellite-based rainfall estimation and discharge measurement of Middle Indus River, Pakistan - Syed Muhammad Zubair Younis; Muhammad Majid; Ahmad Ammar (Arabian Journal of Geosciences, 2017)

Evaluation of short-term health effects among rural women and reduction in household air pollution due to improved cooking stoves: quasi experimental study - Tanzil Jamali; Zafar Fatmi; Afshan Shahid; Aneeta Khoso; Muhammad Masood Kadir; Nalini Sathiakumar (Air Quality, Atmosphere & Health, 2017)

Erratum to: An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2017)

Effects of different temperature regimes on survival of Diaphorina citri and its endosymbiotic bacterial communities - Mubasher Hussain; Komivi Senyo Akutse; Keppanan Ravindran; Yongwen Lin; Bamisope Steve Bamisile; Muhammad Qasim; Chandra Kanta Dash; Liande Wang (Environmental Microbiology, 2017)
The Asian citrus psyllid, Diaphorina citri , is a major pest of citrus and vector of citrus greening (huanglongbing) in Asian. In our field‐collected psyllid samples, we discovered that Fuzhou (China) and Faisalabad (Pakistan), populations harbored an obligate primary endosymbiont Candidatus Carsonella (gen. nov.) with a single species, Candidatus Carsonella ruddii (sp. nov.) and a secondary endosymbiont, Wolbachia surface proteins (WSP) which are intracellular endosymbionts residing in the bacteriomes. Responses of these symbionts to different temperatures were examined and their host survival assessed. Diagnostic PCR assays showed that the endosymbionts infection rates were not significantly reduced in both D. citri populations after 24 h exposure to cold or heat treatments. Although quantitative PCR assays showed significant reduction of WSP relative densities at 40°C for 24 h, a substantial decrease occurred as the exposure duration increased beyond 3 days. Under the same temperature regimes, Ca. C. ruddii density was initially less affected during the first exposure day, but rapidly reduced at 3–5 days compared to WSP. However, the mortality of the psyllids increased rapidly as exposure time to heat treatment increased. The responses of the two symbionts to unfavorable temperature regimes highlight the complex host‐symbionts interactions between D. citri and its associated endosymbionts.

Bacterial Biofilm Communities and Coral Larvae Settlement at Different Levels of Anthropogenic Impact in the Spermonde Archipelago, Indonesia - Pia Kegler; Hauke F. Kegler; Astrid Gärdes; Sebastian C. A. Ferse; Muhammad Lukman; Yustian R. Alfiansah; Christiane Hassenrück; Andreas Kunzmann (Frontiers in Marine Science, 2017)

Effect of Bottom Friction, Wind Drag Coefficient, and Meteorological Forcing in Hindcast of Hurricane Rita Storm Surge Using SWAN + ADCIRC Model - Muhammad Akbar; Simbarashe Kanjanda; Abram Musinguzi (Journal of Marine Science and Engineering, 2017)
An evaluation of the effect of bottom friction, wind drag coefficient, and meteorological forcing is conducted using a tightly coupled wave and circulation model, SWAN + ADCIRC (i.e., Simulating WAves Nearshore + ADvanced CIRCulation), to hindcast the storm surge of Hurricane Rita (2005). Wind drag coefficient formulations of Powell, Zijlema, and Peng & Li are used to calculate wind stresses. Bottom friction and wind drag coefficients are systematically increased and decreased to quantify their impacts on the hindcast. Different meteorological forcing options are applied to study the effect of wind fields on storm surge development and propagation. Simulated water levels are compared with observed data collected from about 150 locations. It is evident that a lower bottom friction causes higher and faster surge propagation, and earlier arrival of inundation peak at locations far from the land fall. Drag coefficients of Powell, with or without a cap of 0.002, and Zijlema produce similar results, while that of Peng & Li slightly overpredicted the surge. Wind fields may cause overprediction or underprediction of the surge, depending on the choice of the wind model. A good agreement is found between Zijlema’s findings and this study; that simultaneously decreasing or increasing both bottom friction and wind drag essentially provides the same hindcast results.

Antimicrobial and antioxidant activities of a new metabolite from Quercus incana - Farah Gul; Khalid Mohammed Khan; Achyut Adhikari; Salman Zafar; Muhammad Akram; Haroon Khan; Muhammad Saeed (Natural Product Research, 2017)

CaMEL and ADCIRC Storm Surge Models—A Comparative Study - Muhammad Akbar; Richard Luettich; Jason Fleming; Shahrouz Aliabadi (Journal of Marine Science and Engineering, 2017)
The Computation and Modeling Engineering Laboratory (CaMEL), an implicit solver-based storm surge model, has been extended for use on high performance computing platforms. An MPI (Message Passing Interface) based parallel version of CaMEL has been developed from the previously existing serial version. CaMEL uses hybrid finite element and finite volume techniques to solve shallow water conservation equations in either a Cartesian or a spherical coordinate system and includes hurricane-induced wind stress and pressure, bottom friction, the Coriolis effect, and tidal forcing. Both semi-implicit and fully-implicit time stepping formulations are available. Once the parallel implementation is properly validated, CaMEL is evaluated against ADCIRC, an established storm surge model, using a hindcast of storm surge due to Hurricane Katrina. Observed high water marks are used to verify that both models have comparable accuracy. The effects of time step on the stability and accuracy of the models are investigated and indicate that the semi- and fully-implicit solvers in CaMEL allow the use of larger timesteps than ADCIRC’s explicit and semi-implicit solvers. However, ADCIRC outperforms CaMEL in parallel scalability and execution wall clock times. Wall times of CaMEL improve significantly when the largest stable time step sizes are used in respective models, although ADCIRC still is faster.

Reaction Mechanism and Degradation Pathway of Rhodamine 6G by Photocatalytic Treatment - Tahir Rasheed; Muhammad Bilal; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Water, Air, & Soil Pollution, 2017)

A Dialogue on Perspectives of Biochar Applications and Its Environmental Risks - Samia Qadeer; Muzammil Anjum; Azeem Khalid; Muhammad Waqas; Aniqa Batool; Tariq Mahmood (Water, Air, & Soil Pollution, 2017)

Diurnal thermoregulatory responses in pregnant Yankasa ewes to the dry season in a tropical Savannah - Lukuman Surakat Yaqub; Joseph Olusegun Ayo; Muhammad Umar Kawu; Peter Ibrahim Rekwot (Tropical Animal Health and Production, 2017)

TNFα-induced DLK activation contributes to apoptosis in the beta-cell line HIT - Svenja Börchers; Rohollah Babaei; Catarina Klimpel; Jorge Duque Escobar; Sabine Schröder; Roland Blume; Muhammad Nasir Hayat Malik; Elke Oetjen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Determinants of flood risk mitigation strategies at household level: a case of Khyber Pakhtunkhwa (KP) province, Pakistan - Ashfaq Ahmad Shah; Jingzhong Ye; Muhammad Abid; Raza Ullah (Natural Hazards, 2017)

Synthesis, computational studies and biological evaluation of new 1-acetyl-3-aryl thiourea derivatives as potent cholinesterase inhibitors - Aamer Saeed; Muhammad Shakil Shah; Fayaz Ali Larik; Shafi Ullah Khan; Pervaiz Ali Channar; Ulrich Flörke; Jamshed Iqbal (Medicinal Chemistry Research, 2017)

Seed health of organic peas and faba beans and its effects on the health of the harvested grains - Muhammad Farhan Saeed; Jelena Baćanović; Christian Bruns; Harald Schmidt; Maria Renate Finckh (Journal of Plant Diseases and Protection, 2017)

Comparative studies of three novel freshwater microalgae strains for synthesis of silver nanoparticles: insights of characterization, antibacterial, cytotoxicity and antiviral activities - Muneeba Khalid; Nauman Khalid; Iftikhar Ahmed; Rumeza Hanif; Muhammad Ismail; Hussnain Ahmed Janjua (Journal of Applied Phycology, 2017)

In vitro propagation, genetic stability, and secondary metabolite analysis of wild lavender (Lavandula coronopifolia Poir.) - Wesam Al Khateeb; Razan Kanaan; Tamam El-Elimat; Muhammad Alu’datt; Jamil Lahham; Ahmad El-Oqlah (Horticulture, Environment, and Biotechnology, 2017)

Exogenous silicon application alleviates salt stress in okra - Tahira Abbas; Abdul Sattar; Muhammad Ijaz; Muhammad Aatif; Samina Khalid; Ahmad Sher (Horticulture, Environment, and Biotechnology, 2017)

Biology and management of Avena fatua and Avena ludoviciana: two noxious weed species of agro-ecosystems - Ali Ahsan Bajwa; Muhammad Javaid Akhter; Nadeem Iqbal; Arslan Masood Peerzada; Zarka Hanif; Sudheesh Manalil; Saima Hashim; Hafiz Haider Ali; Lynda Kebaso; David Frimpong; Halima Namubiru; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Biochars mitigate greenhouse gas emissions and bioaccumulation of potentially toxic elements and arsenic speciation in Phaseolus vulgaris L. - Muhammad Ibrahim; Gang Li; Sardar Khan; Qiaoqiao Chi; Yaoyang Xu (Environmental Science and Pollution Research, 2017)

Leaching of phthalate esters from different drinking stuffs and their subsequent biodegradation - Muhammad Ali Surhio; Farah N. Talpur; Shafi M. Nizamani; Marvi Kanwal Talpur; Hassan Imran Afridi; Abid Ali Khaskheli; Shazia Bhurgri; Junaid Ali Surhio (Environmental Science and Pollution Research, 2017)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Characteristics of volatile compound emission and odor pollution from municipal solid waste treating/disposal facilities of a city in Eastern China - Hanwen Guo; Zhenhan Duan; Yan Zhao; Yanjun Liu; Muhammad Farooq Mustafa; Wenjing Lu; Hongtao Wang (Environmental Science and Pollution Research, 2017)

Currently used organophosphate and brominated flame retardants in the environment of China and other developing countries (2000–2016) - Nadeem Ali; Khurram Shahzad; Muhammad Imtiaz Rashid; Heqing Shen; Iqbal Mohammad Ibrahim Ismail; Syed Ali Musstjab Akber Shah Eqani (Environmental Science and Pollution Research, 2017)

Modeling of Cr contamination in the agricultural lands of three villages near the leather industry in Kasur, Pakistan, using statistical and GIS techniques - Muhammad Shafiq; Tahira Shaukat; Aisha Nazir; Firdaus-e- Bareen (Environmental Monitoring and Assessment, 2017)

Community-based participatory research for the study of air pollution: a review of motivations, approaches, and outcomes - Adwoa Commodore; Sacoby Wilson; Omar Muhammad; Erik Svendsen; John Pearce (Environmental Monitoring and Assessment, 2017)

Quality of tube well water intended for irrigation and human consumption with special emphasis on arsenic contamination at the area of Punjab, Pakistan - Atta Rasool; Tangfu Xiao; Abida Farooqi; Muhammad Shafeeque; Yizhang Liu; Muhammad Aqeel Kamran; Ioannis A. Katsoyiannis; Syed Ali Musstjab Akber Shah Eqani (Environmental Geochemistry and Health, 2017)

Occurrence, enantiomeric signature and ecotoxicological risk assessment of HCH isomers and DDT metabolites in the sediments of Kabul River, Pakistan - Muhammad Aamir; Sardar Khan; Lili Niu; Siyu Zhu; Anwarzeb Khan (Environmental Geochemistry and Health, 2017)

Aflatoxin B1 Induced Systemic Toxicity in Poultry and Rescue Effects of Selenium and Zinc - Muhammad Jameel Mughal; Xi Peng; Asghar Ali Kamboh; Yi Zhou; Jing Fang (Biological Trace Element Research, 2017)

Rapid injuries of high temperature in plants - Gurpreet Kaur Goraya; Balraj Kaur; Bavita Asthir; Shashi Bala; Gurpreet Kaur; Muhammad Farooq (Journal of Plant Biology, 2017)

Application of spectral decomposition for the detection of fluvial sand reservoirs, Indus Basin, SW Pakistan - Muhammad N. Tayyab; Shazia Asim (Geosciences Journal, 2017)

Terbufos sulfone aggravates kidney damage in STZ-induced diabetic rats - Syed Muhammad Nurulain; Shreesh Ojha; Mohamed Shafiullah; Javed Yasin; Tayyaba Yasmin; Tariq Saeed; Ernest Adeghate (Biologia, 2017)

Characterization of five-year observation data of fine particulate matter in the metropolitan area of Lahore - Fatima Khanum; Muhammad Nawaz Chaudhry; Prashant Kumar (Air Quality, Atmosphere & Health, 2017)

Foliar application of selenium increases fertility and grain yield in bread wheat under contrasting water availability regimes - Iram Shahzadi; Muhammad Iqbal; Rizwan Rasheed; M. Arslan Ashraf; Shagufta Perveen; Makhdoom Hussain (Acta Physiologiae Plantarum, 2017)

RNA-Seq reveals differential expression patterns of genes associated with carotenoid accumulation in loquat - Ting-ting Zheng; Zhi-ke Zhang; Muhammad Qasim Shahid; Wei-ling Wei; Faheem Shehzad Baloch; Jin-cheng Wu; Shun-quan Lin; Xiang-hui Yang (Acta Physiologiae Plantarum, 2017)

Effect of Rheology and Poloxamers Properties on Release of Drugs from Silicon Dioxide Gel-Filled Hard Gelatin Capsules—A Further Enhancement of Viability of Liquid Semisolid Matrix Technology - Misbah Sultana; Mobashar Ahmad Butt; Tariq Saeed; Rizwan Mahmood; Saeed ul Hassan; Khalid Hussain; Syed Atif Raza; Muhammad Ahsan; Nadeem Irfan Bukhari (AAPS PharmSciTech, 2017)

Evaporation modelling using different machine learning techniques - Lunche Wang; Ozgur Kisi; Bo Hu; Muhammad Bilal; Mohammad Zounemat‐Kermani; Hui Li (International Journal of Climatology, 2017)
Accurate prediction of pan evaporation ( Ep ) is critical for water resource management. This article investigates the capabilities of three different soft computing methods at estimating monthly Ep at six stations in the Yangtze River Basin using climatic factors, including the air temperature ( Ta ), solar radiation ( Rg ), air pressure ( Pa ) and wind speed ( Ws ) for the period of 1961–2000. The first part of the study focused on testing and comparing model accuracy levels at each station using local input combinations. The results indicate that the fuzzy genetic ( FG ) model generally produces better results than adaptive neuro‐fuzzy inference systems with grid partition (ANFIS‐GP) and M5 model tree ( M5Tree ) specifications in terms of the root mean square error , mean absolute error and coefficient of determination values. The performance of the above models was also examined using cross‐station applications (estimating Ep without local input or output data) in the second part of the study. The third part focused on estimating Ep using generalized FG , ANFIS‐GP and M5Tree models. Collectively, the results demonstrate that the FG model can be successfully used to estimate Ep without any local inputs and outputs and that a single generalized FG model can also be used at six different locations.

Variants in the PRPF8 Gene are Associated with Glaucoma - Shazia Micheal; Barend F. Hogewind; Muhammad Imran Khan; Sorath Noorani Siddiqui; Saemah Nuzhat Zafar; Farah Akhtar; Raheel Qamar; Carel B. Hoyng; Anneke I. den Hollander (Molecular Neurobiology, 2017)

A long-term trend in precipitation of different spatial regions of Bangladesh and its teleconnections with El Niño/Southern Oscillation and Indian Ocean Dipole - Md. Kawser Ahmed; Mohammad Samsul Alam; Abu Hena Muhammad Yousuf; Md. Monirul Islam (Theoretical and Applied Climatology, 2017)

Disaster risk management in agriculture: tragedies of the smallholders - Raza Ullah; Ganesh P. Shivakoti; Farhad Zulfiqar; Muhammad Nadeem Iqbal; Ashfaq Ahmad Shah (Natural Hazards, 2017)

Phenacyl group containing amide derivative of dehydroabietylamine exhibiting enhanced cytotoxic activity against PLC and MCF7 cancer cell lines - Muhammad Ayaz Mustufa; Afshan Aslam; Cigdem Ozen; Imran Ali Hashmi; Naim ul Hasan Naqvi; Mehmet Ozturk; Firdous Imran Ali (Medicinal Chemistry Research, 2017)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Nitrogen and plant population change radiation capture and utilization capacity of sunflower in semi-arid environment - Muhammad Awais; Aftab Wajid; Muhammad Usman Bashir; Muhammad Habib-ur-Rahman; Muhammad Aown Sammar Raza; Ashfaq Ahmad; Muhammad Farrukh Saleem; Hafiz Mohkum Hammad; Muhammad Mubeen; Umer Saeed; Muhammad Naveed Arshad; Shah Fahad; et al. (Environmental Science and Pollution Research, 2017)

Phyto-management of Cr-contaminated soils by sunflower hybrids: physiological and biochemical response and metal extractability under Cr stress - Mujahid Farid; Shafaqat Ali; Nudrat Aisha Akram; Muhammad Rizwan; Farhat Abbas; Syed Asad Hussain Bukhari; Rashid Saeed (Environmental Science and Pollution Research, 2017)

The use of wastewater in livestock production and its socioeconomic and welfare implications - Ehsan Elahi; Muhammad Abid; Liqin Zhang; Gibson Maswayi Alugongo (Environmental Science and Pollution Research, 2017)

Growth-corruption-health triaca and environmental degradation: empirical evidence from Indonesia, Malaysia, and Thailand - Muhammad Azam; Abdul Qayyum Khan (Environmental Science and Pollution Research, 2017)

Understanding brassinosteroid-regulated mechanisms to improve stress tolerance in plants: a critical review - Fahim Nawaz; Muhammad Naeem; Bilal Zulfiqar; Asim Akram; Muhammad Yasin Ashraf; Muhammad Raheel; Rana Nauman Shabbir; Rai Altaf Hussain; Irfan Anwar; Muhammad Aurangzaib (Environmental Science and Pollution Research, 2017)

Arsenic accumulation and physiological attributes of spinach in the presence of amendments: an implication to reduce health risk - Muhammad Shahid; Marina Rafiq; Nabeel Khan Niazi; Camille Dumat; Saliha Shamshad; Sana Khalid; Irshad Bibi (Environmental Science and Pollution Research, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Rutin–Nickel Complex: Synthesis, Characterization, Antioxidant, DNA Binding, and DNA Cleavage Activities - Aun Raza; Shumaila Bano; Xiuquan Xu; Rong Xian Zhang; Haider Khalid; Furqan Muhammad Iqbal; Changkun Xia; Jian Tang; Zhen Ouyang (Biological Trace Element Research, 2017)

Manganese nutrition improves the productivity and grain biofortification of fine grain aromatic rice in conventional and conservation production systems - Aman Ullah; Muhammad Farooq; Asif Nadeem; Abdul Rehman; Saeed A. Asad; Ahmad Nawaz (Paddy and Water Environment, 2017)

Allelopathic interference of alfalfa (Medicago sativa L.) genotypes to annual ryegrass (Lolium rigidum) - Hasan Muhammad Zubair; James E. Pratley; G. A. Sandral; A. Humphries (Journal of Plant Research, 2017)

Enzyme inhibitory metabolites from endophytic Penicillium citrinum isolated from Boswellia sacra - Sajid Ali; Abdul Latif Khan; Liaqat Ali; Tania Shamim Rizvi; Sumera Afzal Khan; Javid Hussain; Muhammad Hamayun; Ahmed Al-Harrasi (Archives of Microbiology, 2017)

Felsic dykes in the Neoproterozoic Nagar Parkar Igneous Complex, SE Sindh, Pakistan: geochemistry and tectonic settings - Tahseenullah Khan; Mamoru Murata; M. Qasim Jan; Hafiz Ur Rehman; Muhammad Zafar; Hiroaki Ozawa; Anwar Qadir; Saqib Mehmood (Arabian Journal of Geosciences, 2017)

Temporal changes in trace elements in brown soil and soybean after long-term fertilization - Muhammad Imran Ashraf; Na Li; Xiaori Han; Jinfeng Yang; Yue Wang; Shumao Fan; Muhammad Irshad; Qaisar Mahmood (Arabian Journal of Geosciences, 2017)

Development of Eudragit RS 100 Microparticles Loaded with Ropinirole: Optimization and In Vitro Evaluation Studies - Prince Muhammad Kashif; Asadullah Madni; Muhammad Ashfaq; Mubashar Rehman; Muhammad Ahmad Mahmood; Muhammad Imran Khan; Nayab Tahir (AAPS PharmSciTech, 2017)

Ultrasonic Processing Technique as a Green Preparation Approach for Diacerein-Loaded Niosomes - Muhammad Imran Khan; Asadullah Madni; Jouni Hirvonen; Leena Peltonen (AAPS PharmSciTech, 2017)

Water Deficit Irrigation and Nitrogen Response of Sudan Grass under Arid Land Drip Irrigation Conditions - Samir G. Al‐Solaimani; Fahad Alghabari; Muhammad Zahid Ihsan; Shah Fahad (Irrigation and Drainage, 2017)
The present study evaluated the interactive effect of water deficit irrigation (WDI) and nitrogen application on Sorghum sudanense growth, biomass accumulation, nitrogen content and water productivity for two consecutive seasons and three cuts. The WDI of 50, 30 and 10% depletion ratios (different application rate and frequency) along with four levels (0, 100, 200 and 300 kg ha −1 ) of nitrogen fertilizer were applied in three splits. The WDI of 10% depletion ratio recorded significantly higher (15–17%) fresh and dry biomass accumulation of both leaf and stem as compared with WDI of 50%. Nitrogen application improved all growth traits irrespective of the applied levels of WDI, season and cut number. The interaction of WDI of 30% depletion ratio and N200 outcompeted all other treatments for plant nitrogen and protein contents, as the resulting increment was 10–22% higher as compared to control. Of the different cut numbers, the first cutting ascribed the maximum value for plant protein contents and stated up to 32% improvement over second and third cuttings. By increasing the rate of nitrogen application, a significant increment in crop water productivity was also measured that attributed at least a threefold higher value for stem over leaf. In essence, WDI of 10% depletion ratio and nitrogen rate of 200 kg ha −1 were the optimum levels that improved Sudan grass growth, biomass and water use efficiency; moreover, the 30% depletion ratio favoured plant nitrogen content. By using a WDI approach, we can improve our forage yield with a limited amount of water by increasing irrigation frequency. Copyright © 2017 John Wiley & Sons, Ltd.

Hutchinson–Gilford Progeria Syndrome: A Premature Aging Disease - Muhammad Saad Ahmed; Sana Ikram; Nousheen Bibi; Asif Mir (Molecular Neurobiology, 2017)

Electric vehicle and end-of-life vehicle estimation in Malaysia 2040 - Muhammad Azmi; Akihiro Tokai (Environment Systems and Decisions, 2017)

MPD3: a useful medicinal plants database for drug designing - Arooj Mumtaz; Usman Ali Ashfaq; Muhammad Tahir ul Qamar; Farooq Anwar; Faisal Gulzar; Muhammad Amjad Ali; Nazamid Saari; Muhammad Tariq Pervez (Natural Product Research, 2017)

A new glycosidic antioxidant from Ranunculus muricatus L. (Ranunculaceae) exhibited lipoxygenasae and xanthine oxidase inhibition properties - Naila Raziq; Muhammad Saeed; Muhammad Shaiq Ali; Salman Zafar; Muhammad Shahid; Mehreen Lateef (Natural Product Research, 2017)

Ethnoveterinary health management practices using medicinal plants in South Asia – a review - Shanoo Suroowan; Faisal Javeed; Mushtaq Ahmad; Muhammad Zafar; Mehwish Jamil Noor; Sadaf Kayani; Ali Javed; Mohamad Fawzi Mahomoodally (Veterinary Research Communications, 2017)

Prevalence of antibodies to Neospora caninum in the serum of camels (Camelus dromedarius) from central Punjab, Pakistan - Muhammad Mudasser Nazir; Muhammad Oneeb; Muhammad Mazhar Ayaz; Fehmeeda Bibi; Atif Nisar Ahmad; Abdul Waheed; Muhammad Afzal Sajid; Muhammad Tauseef Sultan; Ghulam Yasin; David S. Lindsay (Tropical Animal Health and Production, 2017)

Effect of Loading Rate on the Felicity Effect of Three Rock Types - Yu Zhang; Yulong Chen; Rangang Yu; Liangqiang Hu; Muhammad Irfan (Rock Mechanics and Rock Engineering, 2017)

Vulnerability assessment of an agro-stressed aquifer using a source-pathway-receptor model in GIS - Yawar Hussain; Sadia F. Ullah; Abdul Q. Aslam; Muhammad B. Hussain; Gulraiz Akhter; Hernan E. Martinez-Carvajal; Frédéric Satgé; Arshad Ashraf; Bilal Iqbal; Martin Cárdenas-Soto (Modeling Earth Systems and Environment, 2017)

Fasting leptin and glucose in normal weight, over weight and obese men and women diabetes patients with and without clinical depression - Darakhshan Jabeen Haleem; Shehnaz Sheikh; Asher Fawad; Muhammad A. Haleem (Metabolic Brain Disease, 2017)

Phytochemical screening, acute toxicity, anxiolytic and antidepressant activities of the Nelumbo nucifera fruit - Muhammad Ali Rajput; Rafeeq Alam Khan (Metabolic Brain Disease, 2017)

Distribution of root-knot nematode species and their virulence on vegetables in northern temperate agro-ecosystems of the Pakistani-administered territories of Azad Jammu and Kashmir - Muhammad Tariq-Khan; Anjum Munir; Tariq Mukhtar; Johannes Hallmann; Holger Heuer (Journal of Plant Diseases and Protection, 2017)

Effect of Ferrule Height and Post Length on Mechanical Stress and Displacement of Endodontically Treated Maxillary Central Incisor: A Finite Element Analysis - Muhammad Ikman Ishak; Aisyah Ahmad Shafi; Mohammed Rafiq Abdul Kadir; Eshamsul Sulaiman (Journal of Medical and Biological Engineering, 2017)

HCV-induced regulatory alterations of IL-1β, IL-6, TNF-α, and IFN-ϒ operative, leading liver en-route to non-alcoholic steatohepatitis - Rabia Nawaz; Sadia Zahid; Muhammad Idrees; Shazia Rafique; Muhammad Shahid; Ammara Ahad; Iram Amin; Iqra Almas; Samia Afzal (Inflammation Research, 2017)

Response of cotton genotypes to water and heat stress: from field to genes - Muhammad Iqbal; Sami Ul-Allah; Muhammad Naeem; Muhammad Ijaz; Abdul Sattar; Ahmad Sher (Euphytica, 2017)

Occupational and life-style factors-acquired mutagenicity in agric-workers of northeastern Brazil - Tatiana Vieira Souza Chaves; Muhammad Torequl Islam; Manoel Odoríco de Moraes; Marcus Vinícius Oliveira Barros de Alencar; Débora Cássia Vieira Gomes; Rodrigo Mendes de Carvalho; Sharbel Weider Maluf; Fabrício Pires de Moura do Amaral; Márcia Fernanda Correia Jardim Paz; Gilberto Santos Cerqueira; Hercília Maria Lins Rolim; João Marcelo de Castro e Sousa; et al. (Environmental Science and Pollution Research, 2017)

Characterization of rainwater chemical composition after a Southeast Asia haze event: insight of transboundary pollutant transport during the northeast monsoon - Mohd Shahrul Mohd Nadzir; Chin Yik Lin; Md Firoz Khan; Mohd Talib Latif; Doreena Dominick; Haris Hafizal Abdul Hamid; Noorlin Mohamad; Khairul Nizam Abdul Maulud; Muhammad Ikram Abdul Wahab; Nurul Farahana Kamaludin; Mohamad Azwani Shah Mat Lazim (Environmental Science and Pollution Research, 2017)

Biological control of broad-leaved dock infestation in wheat using plant antagonistic bacteria under field conditions - Tasawar Abbas; Zahir Ahmad Zahir; Muhammad Naveed; Zubair Aslam (Environmental Science and Pollution Research, 2017)

Application of chemical oxidation to remediate HCH-contaminated soil under batch and flow through conditions - Muhammad Usman; Oriane Tascone; Victoria Rybnikova; Pierre Faure; Khalil Hanna (Environmental Science and Pollution Research, 2017)

Nitrogen fertility and abiotic stresses management in cotton crop: a review - Aziz Khan; Daniel Kean Yuen Tan; Muhammad Zahir Afridi; Honghai Luo; Shahbaz Atta Tung; Mir Ajab; Shah Fahad (Environmental Science and Pollution Research, 2017)

Environment polluting conventional chemical control compared to an environmentally friendly IPM approach for control of diamondback moth, Plutella xylostella (L.), in China: a review - Muhammad Shakeel; Muhammad Farooq; Wajid Nasim; Waseem Akram; Fawad Zafar Ahmad Khan; Waqar Jaleel; Xun Zhu; Haichen Yin; Shuzhong Li; Shah Fahad; Saddam Hussain; Bhagirath Singh Chauhan; et al. (Environmental Science and Pollution Research, 2017)

Enzyme-based solutions for textile processing and dye contaminant biodegradation—a review - Shahzad Ali Shahid Chatha; Muhammad Asgher; Hafiz M. N. Iqbal (Environmental Science and Pollution Research, 2017)

Cytotoxicity and genotoxicity of Guaribas river water (Piauí, Brazil), influenced by anthropogenic action - João Marcelo de Castro e Sousa; Ana Paula Peron; Louridânya da Silva e Sousa; Mércia de Moura Holanda; Ataíde de Macedo Vieira Lima; Vitor Alves de Oliveira; Felipe Cavalcanti Carneiro da Silva; Leonardo Henrique Guedes de Morais Lima; Leomá Albuquerque Matos; Sandra Maria Mendes de Moura Dantas; Raí Pablo Sousa de Aguiar; Muhammad Torequl Islam; et al. (Environmental Monitoring and Assessment, 2017)

Comparison of rhizosphere properties as affected by different Bt- and non-Bt-cotton (Gossypium hirsutum L.) genotypes and fertilization - Maqshoof Ahamd; Waleed Mumtaz Abbasi; Moazzam Jamil; Muhammad Iqbal; Azhar Hussain; Muhammad Fakhar-u-Zaman Akhtar; Farheen Nazli (Environmental Monitoring and Assessment, 2017)

Retraction Note to: Estimation of Anticipated Performance Index and Air Pollution Tolerance Index and of vegetation around the marble industrial areas of Potwar region: bioindicators of plant pollution response - Mehwish Jamil Noor; Shazia Sultana; Sonia Fatima; Mushtaq Ahmad; Muhammad Zafar; Maliha Sarfraz; Masour A. Balkhyour; Sher Zaman Safi; Muhammad Aqeel Ashraf (Environmental Geochemistry and Health, 2017)

Retraction Note to: Release, deposition and elimination of radiocesium (137Cs) in the terrestrial environment - Muhammad Aqeel Ashraf; Ayesha Masood Khan; Mushtaq Ahmad; Shatirah Akib; Khaled S. Balkhair; Nor Kartini Abu Bakar (Environmental Geochemistry and Health, 2017)

Levels of Organotin Compounds in Selected Fish Species from the Arabian Gulf - Muhammad Waqar Ashraf; Abdus Salam; Atiq Mian (Bulletin of Environmental Contamination and Toxicology, 2017)

A Novel Idea to Improve Cardiac Output of Mechanical Circulatory Support Devices by Optimizing Kinetic Energy Transfer Available in Forward Moving Aortic Blood Flow - Muhammad B. Qureshi; Jacob Glower; Daniel L. Ewert; Steven C. Koenig (Cardiovascular Engineering and Technology, 2017)

Effect of Loss of Heart Rate Variability on T-Wave Heterogeneity and QT Variability in Heart Failure Patients: Implications in Ventricular Arrhythmogenesis - Sachin Nayyar; Muhammad A. Hasan; Kurt C. Roberts-Thomson; Thomas Sullivan; Mathias Baumert (Cardiovascular Engineering and Technology, 2017)

Molecular genetic analysis of consanguineous families with primary microcephaly identified pathogenic variants in the ASPM gene - MUZAMMIL AHMAD KHAN; CHRISTIAN WINDPASSINGER; MUHAMMAD ZEESHAN ALI; MUHAMMAD ZUBAIR; HADIA GUL; SAFDAR ABBAS; SAADULLAH KHAN; MUHAMMAD BADAR; RAMZI M. MOHAMMAD; ZAFAR NAWAZ (Journal of Genetics, 2017)

Degradation of Pharmaceuticals and Personal Care Products by White-Rot Fungi—a Critical Review - Muhammad B. Asif; Faisal I. Hai; Lakhveer Singh; William E. Price; Long D. Nghiem (Current Pollution Reports, 2017)

High-resolution regional gravity field model of Pakistan based on best residual terrain model (RTM) of topography and interpolation techniques - Muhammad Sadiq; Aneeque A. Qazi; M. Ramzan (Arabian Journal of Geosciences, 2017)

Generic hierarchy of sandstone facies quality and static connectivity: an example from the Middle-Late Miocene Miri Formation, Sarawak Basin, Borneo - Numair A. Siddiqui; Abdul Hadi A. Rahman; Chow W. Sum; Manoj J. Mathew; Muhammad Hassaan; David Menier (Arabian Journal of Geosciences, 2017)

Does exogenous application of ascorbic acid modulate growth, photosynthetic pigments and oxidative defense in okra (Abelmoschus esculentus (L.) Moench) under lead stress? - Iqbal Hussain; Asif Siddique; Muhammad Arslan Ashraf; Rizwan Rasheed; Muhammad Ibrahim; Muhammad Iqbal; Sobia Akbar; Muhammad Imran (Acta Physiologiae Plantarum, 2017)

Cytotoxic cardiac glycosides from the fruit (pods) of Adenium obesum (Forssk.) Roem. & Schult - Salman Khalid Ahmed; Muhammad Ali Versiani; Ambreen Ikram; Samina Abdul Sattar; Shaheen Faizi (Natural Product Research, 2017)

Electrical Conductivity of Partially Saturated Packings of Particles - Behzad Ghanbarian; Muhammad Sahimi (Transport in Porous Media, 2017)

Ginsenoside F1 attenuates lipid accumulation and triglycerides content in 3T3-L1 adipocytes with the modulation of reactive oxygen species (ROS) production through PPAR-γ/JAK2 signaling responses - Shakina Yesmin Simu; Muhammad Hanif Siddiqi; Sungeun Ahn; Verónica Castro-Aceituno; Natarajan Sathish Kumar; Zuly Elizabeth Jimenez Perez; Deok-Chun Yang (Medicinal Chemistry Research, 2017)

Synthesis of 2-phenyl-1H-imidazo[4,5-b]pyridine as type 2 diabetes inhibitors and molecular docking studies - Muhammad Taha; Nor Hadiani Ismail; Syahrul Imran; Izzatul Ainaa; Manikandan Selvaraj; Mohd syukri baharudin; Muhammad Ali; Khalid Mohammed Khan; Nizam Uddin (Medicinal Chemistry Research, 2017)

Classification of ankle joint movements based on surface electromyography signals for rehabilitation robot applications - Maged S. AL-Quraishi; Asnor J. Ishak; Siti A. Ahmad; Mohd K. Hasan; Muhammad Al-Qurishi; Hossein Ghapanchizadeh; Atif Alamri (Medical & Biological Engineering & Computing, 2017)

Chromium tolerance, oxidative stress response, morphological characteristics, and FTIR studies of phytopathogenic fungus Sclerotium rolfsii - Shahid Rafi; Amna Shoaib; Zoia Arshad Awan; Nayab Batool Rizvi; Nafisa; Muhammad Shafiq (Folia Microbiologica, 2017)

Osmopriming with CaCl2 improves wheat (Triticum aestivum L.) production under water-limited environments - Shahid Farooq; Mubshar Hussain; Khawar Jabran; Waseem Hassan; Muhammad S. Rizwan; Tauqeer A. Yasir (Environmental Science and Pollution Research, 2017)

The dynamic relationship between structural change and CO2 emissions in Malaysia: a cointegrating approach - Wajahat Ali; Azrai Abdullah; Muhammad Azam (Environmental Science and Pollution Research, 2017)

Water-saving technologies affect the grain characteristics and recovery of fine-grain rice cultivars in semi-arid environment - Khawar Jabran; Muhammad Riaz; Mubshar Hussain; Wajid Nasim; Umar Zaman; Shah Fahad; Bhagirath Singh Chauhan (Environmental Science and Pollution Research, 2017)

Current advancements of magnetic nanoparticles in adsorption and degradation of organic pollutants - Mazhar Ul-Islam; Muhammad Wajid Ullah; Shaukat Khan; Shehrish Manan; Waleed Ahmad Khattak; Wasi Ahmad; Nasrullah Shah; Joong Kon Park (Environmental Science and Pollution Research, 2017)

Biochar soil amendment on alleviation of drought and salt stress in plants: a critical review - Shafaqat Ali; Muhammad Rizwan; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Ibrahim; Muhammad Riaz; Muhammad Saleem Arif; Farhan Hafeez; Mohammad I. Al-Wabel; Ahmad Naeem Shahzad (Environmental Science and Pollution Research, 2017)

Effectiveness of carbon dioxide against different developmental stages of Cadra cautella and Tribolium castaneum - Mureed Husain; Sukirno Sukirno; Khalid Mehmood; Muhammad Tufail; Khawaja Ghulam Rasool; Waleed Saleh Alwaneen; Abdulrahman Saad Aldawood (Environmental Science and Pollution Research, 2017)

Role of brassinosteroids in alleviating toxin-induced stress of Verticillium dahliae on cotton callus growth - Noreen Bibi; Imrul Mosaddek Ahmed; Kai Fan; Muhammad Dawood; Feng Li; Shuna Yuan; Xuede Wang (Environmental Science and Pollution Research, 2017)

Skill and predictability in multimodel ensemble forecasts for Northern Hemisphere regions with dominant winter precipitation - Muhammad Azhar Ehsan; Michael K. Tippett; Mansour Almazroui; Muhammad Ismail; Ahmed Yousef; Fred Kucharski; Mohamed Omar; Mahmoud Hussein; Abdulrahman A. Alkhalaf (Climate Dynamics, 2017)

Are Karakoram temperatures out of phase compared to hemispheric trends? - Fayaz Asad; Haifeng Zhu; Hui Zhang; Eryuan Liang; Sher Muhammad; Suhaib Bin Farhan; Iqtidar Hussain; Muhammad Atif Wazir; Moinuddin Ahmed; Jan Esper (Climate Dynamics, 2017)

miRNAs: Major modulators for crop growth and development under abiotic stresses - Ali Noman; Shah Fahad; Muhammad Aqeel; Usman Ali; Amanullah; Sumera Anwar; Shahbaz Khan Baloch; Madiha Zainab (Biotechnology Letters, 2017)

Structural and functional characteristics of plant proteinase inhibitor-II (PI-II) family - Shazia Rehman; Ejaz Aziz; Wasim Akhtar; Muhammad Ilyas; Tariq Mahmood (Biotechnology Letters, 2017)

Single and Combined Impacts of Vitamin A and Selenium in Diet on Productive Performance, Egg Quality, and Some Blood Parameters of Laying Hens During Hot Season - Mohamed E. Abd El-Hack; Khalid Mahrose; Ali A. Askar; Mahmoud Alagawany; Muhammad Arif; Muhammad Saeed; Farzana Abbasi; Rab Nawaz Soomro; Farman Ali Siyal; Maria Tabassum Chaudhry (Biological Trace Element Research, 2017)

Ectomycorrhizal fungal diversity associated with endemic Tristaniopsis spp. (Myrtaceae) in ultramafic and volcano-sedimentary soils in New Caledonia - Muhammad Waseem; Marc Ducousso; Yves Prin; Odile Domergue; Laure Hannibal; Clarisse Majorel; Philippe Jourand; Antoine Galiana (Mycorrhiza, 2017)

Exogenous application of urea and a urease inhibitor improves drought stress tolerance in maize (Zea mays L.) - Wei Gou; Pufan Zheng; Li Tian; Mei Gao; Lixin Zhang; Nudrat Aisha Akram; Muhammad Ashraf (Journal of Plant Research, 2017)

Identification of a novel copper-activated and halide-tolerant laccase in Geobacillus thermopakistaniensis - Saadia Basheer; Naeem Rashid; Raza Ashraf; Muhammad Sohail Akram; Masood Ahmed Siddiqui; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Pcal_0111, a highly thermostable bifunctional fructose-1,6-bisphosphate aldolase/phosphatase from Pyrobaculum calidifontis - Iram Aziz; Naeem Rashid; Raza Ashraf; Qamar Bashir; Tadayuki Imanaka; Muhammad Akhtar (Extremophiles, 2017)

Molecular characterization of previously elusive badnaviruses associated with symptomatic cacao in the New World - Nomatter Chingandu; Muhammad Zia-ur-rehman; Thyail N. Sreenivasan; Surendra Surujdeo-Maharaj; Pathmanathan Umaharan; Osman A. Gutierrez; Judith K. Brown (Archives of Virology, 2017)

Continuous wavelet transforms of spectral decomposition analyses for fluvial reservoir characterization of Miano Gas Field, Indus Platform, Pakistan - Muhammad Tayyab Naseer; Shazia Asim (Arabian Journal of Geosciences, 2017)

Trypsinized Cry1Fa and Vip3Aa have no detrimental effects on the adult green lacewing Chrysopa pallens (Neuroptera: Chrysopidae) - Intazar Ali; Shuai Zhang; Muhammad Iqbal; Samina Ejaz; Jin-jie Cui (Applied Entomology and Zoology, 2017)

Formulation and In Vitro Characterization of Thiolated Buccoadhesive Film of Fluconazole - Kiran Naz; Gul Shahnaz; Naveed Ahmed; Naveeda Akhtar Qureshi; Hafiz Shoaib Sarwar; Muhammad Imran; Gul Majid Khan (AAPS PharmSciTech, 2017)

Development and Optimization of an Ex Vivo Colloidal Stability Model for Nanoformulations - Muhammad Vaseem Shaikh; Manika Kala; Manish Nivsarkar (AAPS PharmSciTech, 2017)

Attribution of runoff change in the alpine basin: a case study of the Heihe Upstream Basin, China - Zhentao Cong; Muhammad Shahid; Danwu Zhang; Huimin Lei; Dawen Yang (Hydrological Sciences Journal, 2017)

Rainfall Extremes: a Novel Modeling Approach for Regionalization - Muhammad Uzair Qamar; Muhammad Azmat; Muhammad Adnan Shahid; Daniele Ganora; Shakil Ahmad; Muhammad Jehanzeb Masud Cheema; Muhammad Abrar Faiz; Abid Sarwar; Muhammad Shafeeque; Muhammad Imran Khan (Water Resources Management, 2017)

Processes of initial collision and suturing between India and Asia - Lin Ding; Satybaev Maksatbek; FuLong Cai; HouQi Wang; PeiPing Song; WeiQiang Ji; Qiang Xu; LiYun Zhang; Qasim Muhammad; Baral Upendra (Science China Earth Sciences, 2017)

Neuro-psychopharmacological perspective of Orphan receptors of Rhodopsin (class A) family of G protein-coupled receptors - Muhammad Zahid Khan; Ling He (Psychopharmacology, 2017)

Validation of a field-friendly extraction and storage method to monitor fecal steroid metabolites in wild orangutans - Taufiq Purna Nugraha; Michael Heistermann; Muhammad Agil; Bambang Purwantara; Iman Supriatna; Gholib Gholib; Carel P. van Schaik; Tony Weingrill (Primates, 2017)

Impact of Dysdercus koenigii Fabricius (Hemiptera: Pyrrhcoridae) density-dependent population on agronomic and qualitative characteristics of different transgenic cotton varieties - Muhammad Rafiq Shahid; Muhammad Farooq; Muhammad Shakeel; Abid Mahmood; Muhammad Dildar Gogi (Phytoparasitica, 2017)

Genetically transformed tobacco plants expressing synthetic EPSPS gene confer tolerance against glyphosate herbicide - Muhammad Imran; Shaheen Asad; Andre Luiz Barboza; Esteban Galeano; Helaine Carrer; Zahid Mukhtar (Physiology and Molecular Biology of Plants, 2017)

CDK5RAP2 interaction with components of the Hippo signaling pathway may play a role in primary microcephaly - Salil K. Sukumaran; Maria Stumpf; Sarah Salamon; Ilyas Ahmad; Kurchi Bhattacharya; Sarah Fischer; Rolf Müller; Janine Altmüller; Birgit Budde; Holger Thiele; Muhammad Tariq; Naveed Altaf Malik; et al. (Molecular Genetics and Genomics, 2017)

Effect of poly-L-arginine in inhibiting scrapie prion protein of cultured cells - Muhammad Waqas; Hye-Mi Lee; Jeeyoung Kim; Glenn Telling; Jin-Ki Kim; Dae-Hwan Kim; Chongsuk Ryou (Molecular and Cellular Biochemistry, 2017)

Appraisal for site specific plant nutrient management through spatial variability and mapping in hilly areas of northern Pakistan - Munir Ahmad; Dost Muhammad; Maria Mussarat; Abid Ali Khan; Shah Faisal Khan; Muhammad Waqas Javed (Journal of Soils and Sediments, 2017)

Reducing nitrogen losses through ammonia volatilization and surface runoff to improve apparent nitrogen recovery of double cropping of late rice using controlled release urea - Pengfei Li; Jianwei Lu; Wenfeng Hou; Yonghui Pan; Yang Wang; Muhammad Rizwan Khan; Tao Ren; Rihuan Cong; Xiaokun Li (Environmental Science and Pollution Research, 2017)

Exogenous application of plant growth regulators (PGRs) induces chilling tolerance in short-duration hybrid maize - Muhammad Ahmed Waqas; Imran Khan; Muhammad Javaid Akhter; Mehmood Ali Noor; Umair Ashraf (Environmental Science and Pollution Research, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)

The key role of biogenic manganese oxides in enhanced removal of highly recalcitrant 1,2,4-triazole from bio-treated chemical industrial wastewater - Ruiqin Wu; Haobo Wu; Xinbai Jiang; Jinyou Shen; Muhammad Faheem; Xiuyun Sun; Jiansheng Li; Weiqing Han; Lianjun Wang; Xiaodong Liu (Environmental Science and Pollution Research, 2017)

Agroforestry: a sustainable environmental practice for carbon sequestration under the climate change scenarios—a review - Farhat Abbas; Hafiz Mohkum Hammad; Shah Fahad; Artemi Cerdà; Muhammad Rizwan; Wajid Farhad; Sana Ehsan; Hafiz Faiq Bakhat (Environmental Science and Pollution Research, 2017)

miRNA-based heavy metal homeostasis and plant growth - Ali Noman; Muhammad Aqeel (Environmental Science and Pollution Research, 2017)

Influence of ameliorating soil acidity with dolomite on the priming of soil C content and CO2 emission - Muhammad Shaaban; Lei Wu; Qi-an Peng; Lukas van Zwieten; Muhammad Afzal Chhajro; Yupeng Wu; Shan Lin; Muhammad Mahmood Ahmed; Muhammad Salman Khalid; Muhammad Abid; Ronggui Hu (Environmental Science and Pollution Research, 2017)

Arsenic uptake, accumulation and toxicity in rice plants: Possible remedies for its detoxification: A review - Hafiz Faiq Bakhat; Zahida Zia; Shah Fahad; Sunaina Abbas; Hafiz Mohkum Hammad; Ahmad Naeem Shahzad; Farhat Abbas; Hesham Alharby; Muhammad Shahid (Environmental Science and Pollution Research, 2017)

Soil compaction effects on soil health and cropproductivity: an overview - Adnan Noor Shah; Mohsin Tanveer; Babar Shahzad; Guozheng Yang; Shah Fahad; Saif Ali; Muhammad Adnan Bukhari; Shahbaz Atta Tung; Abdul Hafeez; Biangkham Souliyanonh (Environmental Science and Pollution Research, 2017)

Assessment of tap water quality and corrosion scales from the selected distribution systems in northern Pakistan - Shams Ali Baig; Zimo Lou; Muzaffar Ali Baig; Muhammad Qasim; Dilawar Farhan Shams; Qaisar Mahmood; Xinhua Xu (Environmental Monitoring and Assessment, 2017)

Assessing impact of effluent discharge on irrigation water quality in southern region of Khyber Pakhtunkhwa, Pakistan - Shabnam Zafar; Azim Khan; Hidayat Ullah; Muhammad Sohail Khan; Ilham Khan; Asma Hameed; Shafeeq Ur Rehman; Ghazala Yasmeen (Environmental Monitoring and Assessment, 2017)

Use of Maize (Zea mays L.) for phytomanagement of Cd-contaminated soils: a critical review - Muhammad Rizwan; Shafaqat Ali; Muhammad Farooq Qayyum; Yong Sik Ok; Muhammad Zia-ur-Rehman; Zaheer Abbas; Fakhir Hannan (Environmental Geochemistry and Health, 2017)

Eco-Friendly Synthesis of Silver Nanoparticles Through Economical Methods and Assessment of Toxicity Through Oxidative Stress Analysis in the Labeo Rohita - Muhammad Saleem Khan; Naureen Aziz Qureshi; Farhat Jabeen; Muhammad Saleem Asghar; Muhammad Shakeel; Muhammad Fakhar -e -Alam (Biological Trace Element Research, 2017)

Microbial decomposition of soil organic matter is mediated by quality and quantity of crop residues: mechanisms and thresholds - Muhammad Shahbaz; Yakov Kuzyakov; Muhammad Sanaullah; Felix Heitkamp; Vladimir Zelenev; Amit Kumar; Evgenia Blagodatskaya (Biology and Fertility of Soils, 2017)

Climate variability and yield risk in South Asia’s rice–wheat systems: emerging evidence from Pakistan - Muhammad Arshad; T. S. Amjath-Babu; Timothy J. Krupnik; Sreejith Aravindakshan; Azhar Abbas; Harald Kächele; Klaus Müller (Paddy and Water Environment, 2017)

A whole-body physiologically based pharmacokinetic (WB-PBPK) model of ciprofloxacin: a step towards predicting bacterial killing at sites of infection - Muhammad W. Sadiq; Elisabet I. Nielsen; Dalia Khachman; Jean-Marie Conil; Bernard Georges; Georges Houin; Celine M. Laffont; Mats O. Karlsson; Lena E. Friberg (Journal of Pharmacokinetics and Pharmacodynamics, 2017)

Petrology and provenance of the Neogene fluvial succession in Pishin Belt (Katawaz Basin) western Pakistan: implications for sedimentation in peripheral forelands basins - Aimal Khan Kasi; Akhtar Muhammad Kassi; Henrik Friis; Razzaq Abdul Manan (Geosciences Journal, 2017)

Characterization and complete genome sequence of a panicovirus from Bermuda grass by high-throughput sequencing - Muhammad N. Tahir; Ben Lockhart; Samuel Grinstead; Dimitre Mollov (Archives of Virology, 2017)

Cenozoic development of southwestern Malay Basin: new insights from subsidence analysis and thermal history - Muhammad Hassaan; Swapan Kumar Bhattacharya; Manoj Joseph Mathew; Numair Ahmed Siddiqui (Arabian Journal of Geosciences, 2017)

Seismic attributes’ application to evaluate the Goru clastics of Indus Basin, Pakistan - Muhammad Naseer Tayyab; Shazia Asim; Muhammad Mass Siddiqui; Muhammad Naeem; Sarfraz Hussain Solange; Farhan Khan Babar (Arabian Journal of Geosciences, 2017)

Increases in leaf nitrogen concentration and leaf area did not enhance spur survival and return bloom in almonds (Prunus dulcis [Mill.] DA Webb) - Sebastian Saa; Eduardo Fernández; Saiful Muhammad; Andres Olivos-Del Río; Theodore M. DeJong; Emilio Laca; Patrick Brown (Acta Physiologiae Plantarum, 2017)

Natural products from Cuscuta reflexa Roxb . with antiproliferation activities in HCT116 colorectal cell lines - Muhammad Riaz; Aishah Bilal; Muhammad Shaiq Ali; Itrat Fatima; Amir Faisal; Muhammad Azhar Sherkheli; Adnan Asghar (Natural Product Research, 2017)

Satellite-sensed tropospheric NO 2 patterns and anomalies over Indus, Ganges, Brahmaputra, and Meghna river basins - Zia ul-Haq; Salman Tariq; Muhammad Ali; Asim Daud Rana; Khalid Mahmood (International Journal of Remote Sensing, 2017)

Generating Synthetic Rainfall Total Using Multivariate Skew-t and Checkerboard Copula of Maximum Entropy - Noor Fadhilah Ahmad Radi; Roslinazairimah Zakaria; Julia Piantadosi; John Boland; Wan Zawiah Wan Zin; Muhammad Az-zuhri Azman (Water Resources Management, 2017)

Impacts of changing climate and snow cover on the flow regime of Jhelum River, Western Himalayas - Muhammad Azmat; Umar Waqas Liaqat; Muhammad Uzair Qamar; Usman Khalid Awan (Regional Environmental Change, 2017)

Genetic polymorphism among five species of Indus River carps on the basis of random amplified polymorphic DNA (RAPD) analysis - Haji Muhammad; Zafar Iqbal; Qamar Bashir (Rendiconti Lincei. Scienze Fisiche e Naturali, 2017)

Using SOTEM Method to Detect BIF Bodies Buried Under Very Thick and Conductive Quaternary Sediments, Huoqiu Deposit, China - Weiying Chen; Guoqiang Xue; Muhammad Younis Khan; Hai Li (Pure and Applied Geophysics, 2017)

Changes in rubisco, cysteine-rich proteins and antioxidant system of spinach (Spinacia oleracea L.) due to sulphur deficiency, cadmium stress and their combination - Rita Bagheri; Javed Ahmad; Humayra Bashir; Muhammad Iqbal; M. Irfan Qureshi (Protoplasma, 2017)

Synthesis, characterization, and in vitro evaluation of the selective P2Y2 receptor antagonist AR-C118925 - Muhammad Rafehi; Joachim C. Burbiel; Isaac Y. Attah; Aliaa Abdelrahman; Christa E. Müller (Purinergic Signalling, 2017)

Effect of Indole-3-Butyric Acid on Clonal Propagation of Mulberry (Morus alba L.) Stem Cuttings: Rooting and Associated Biochemical Changes - Azamal Husen; Muhammad Iqbal; Shadab Naseer Siddiqui; Sayed Sartaj Sohrab; Getinet Masresha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Expression studies of chitinase gene in transgenic potato against Alternaria solani - Anwar Khan; Idrees Ahmad Nasir; Bushra Tabassum; Khadija Aaliya; Muhammad Tariq; Abdul Qayyum Rao (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Maximizing maize quality, productivity and profitability through a combined use of compost and nitrogen fertilizer in a semi-arid environment in Pakistan - Shahid Iqbal; Christian Thierfelder; Haroon Zaman Khan; Hafiz Muhammad Rashad Javeed; Muhammad Arif; Muhammad Shehzad (Nutrient Cycling in Agroecosystems, 2017)

Number of pegs influence focal stress distributions and micromotion in glenoid implants: a finite element study - Abdul Hadi Abdul Wahab; Mohammed Rafiq Abdul Kadir; Muhammad Noor Harun; Tunku Kamarul; Ardiyansyah Syahrom (Medical & Biological Engineering & Computing, 2017)

Biochar for crop production: potential benefits and risks - Mubshar Hussain; Muhammad Farooq; Ahmad Nawaz; Abdullah M. Al-Sadi; Zakaria M. Solaiman; Salem S. Alghamdi; Ume Ammara; Yong Sik Ok; Kadambot H. M. Siddique (Journal of Soils and Sediments, 2017)

Salicylic Acid Induced Salinity Tolerance Through Manipulation of Ion Distribution Rather than Ion Accumulation - Hadi Pirasteh-Anosheh; Yahya Emam; Mohammad Javad Rousta; Muhammad Ashraf (Journal of Plant Growth Regulation, 2017)

Process Understanding in Freeze-Drying Cycle Development: Applications for Through-Vial Impedance Spectroscopy (TVIS) in Mini-pilot Studies - Geoff Smith; Muhammad Sohail Arshad; Eugene Polygalov; Irina Ermolina; Timothy R McCoy; Paul Matejtschuk (Journal of Pharmaceutical Innovation, 2017)

Study of the global and regional climatic impacts of ENSO magnitude using SPEEDY AGCM - Muhammad Mubashar Dogar; Fred Kucharski; Syed Azharuddin (Journal of Earth System Science, 2017)

Population pharmacokinetics of meropenem in elderly patients: dosing simulations based on renal function - Muhammad Usman; Otto R. Frey; Georg Hempel (European Journal of Clinical Pharmacology, 2017)

Pathogenic diversity of Xanthomonas oryzae pv. oryzae isolates collected from Punjab Province of Pakistan - Hafiz Muhammad Imran Arshad; Kamran Saleem; Junaid Ahmed Khan; Muhammad Rashid; Muhammad Atiq; Syed Sarwar Alam; Shahbaz Talib Sahi (European Journal of Plant Pathology, 2017)

Promotive role of 5-aminolevulinic acid on chromium-induced morphological, photosynthetic, and oxidative changes in cauliflower (Brassica oleracea botrytis L.) - Rehan Ahmad; Shafaqat Ali; Fakhir Hannan; Muhammad Rizwan; Muhammad Iqbal; Zaidul Hassan; Nudrat Aisha Akram; Saliha Maqbool; Farhat Abbas (Environmental Science and Pollution Research, 2017)

Influence of UV-A radiation on oxidative stress and antioxidant enzymes in Mythimna separata (Lepidoptera: Noctuidae) - Arif Ali; Muhammad Adnan Rashid; Qiu Ying Huang; Chao-Liang Lei (Environmental Science and Pollution Research, 2017)

Identification and future description of warming signatures over Pakistan with special emphasis on evolution of CO2 levels and temperature during the first decade of the twenty-first century - Khadija Haider; Muhammad Fahim Khokhar; Farrukh Chishtie; Waseem RazzaqKhan; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2017)

Bio-based degradation of emerging endocrine-disrupting and dye-based pollutants using cross-linked enzyme aggregates - Muhammad Bilal; Muhammad Asgher; Hafiz M. N. Iqbal; Hongbo Hu; Xuehong Zhang (Environmental Science and Pollution Research, 2017)

Direct and indirect effects of wastewater use and herd environment on the occurrence of animal diseases and animal health in Pakistan - Ehsan Elahi; Liqin Zhang; Muhammad Abid; Muhammad Tariq Javed; Han Xinru (Environmental Science and Pollution Research, 2017)

Microelectrophoretic study of environmentally induced DNA damage in fish and its use for early toxicity screening of freshwater bodies - Bilal Hussain; Tayyaba Sultana; Salma Sultana; K. A. Al-Ghanim; Shahreef Masood; Muhammad Ali; Shahid Mahboob (Environmental Monitoring and Assessment, 2017)

Occurrence and methods to remove arsenic and fluoride contamination in water - Sadia Bibi; Muhammad Aqeel Kamran; Jawairia Sultana; Abida Farooqi (Environmental Chemistry Letters, 2017)

Exogenous triacontanol-mediated increase in phenolics, proline, activity of nitrate reductase, and shoot k+ confers salt tolerance in maize (Zea mays L.) - Shagufta Perveen; Muhammad Iqbal; Abida Parveen; Muhammad Sohail Akram; Muhammad Shahbaz; Shehnal Akber; Aneeqa Mehboob (Brazilian Journal of Botany, 2017)

Correlation of Cadmium and Magnesium in the Blood and Serum Samples of Smokers and Non-Smokers Chronic Leukemia Patients - Noman Khan; Hasan Imran Afridi; Tasneem Gul Kazi; Muhammad Balal Arain; Muhammad Bilal; Asma Akhtar; Mustafa Khan (Biological Trace Element Research, 2017)

Persistent outbreaks of the “black disease” sponge Terpios hoshinota in Indonesian coral reefs - Hawis Madduppa; Peter J. Schupp; Muhammad Reza Faisal; Mustami Yuda Sastria; Carsten Thoms (Marine Biodiversity, 2017)

Characterization of carbon monoxide, methane and nonmethane hydrocarbons in emerging cities of Saudi Arabia and Pakistan and in Singapore - Barbara Barletta; Isobel J. Simpson; Nicola J. Blake; Simone Meinardi; Louisa K. Emmons; Omar S. Aburizaiza; Azhar Siddique; Jahan Zeb; Liya E. Yu; Haider A. Khwaja; Muhammad A. Farrukh; Donald R. Blake (Journal of Atmospheric Chemistry, 2017)

Respiratory syncytial virus and influenza are the key viral pathogens in children <2 years hospitalized with bronchiolitis and pneumonia in Islamabad Pakistan - Uzma Bashir; Nadia Nisar; Yasir Arshad; Muhammad Masroor Alam; Asiya Ashraf; Hajra Sadia; Birjees Mazher Kazi; Syed Sohail Zahoor Zaidi (Archives of Virology, 2017)

Comparative study of performance of real-time satellite-derived rainfall in Swat Catchment - Muhammad Umar; Adil Latif; Syed Amer Mahmood (Arabian Journal of Geosciences, 2017)

A new irregular monoterpene acetate along with eight known compounds with antifungal potential from the aerial parts of Artemisia incisa Pamp (Asteraceae) - Mamoon Ur Rashid; Muhammad Alamzeb; Saqib Ali; Zafar Ali Shah; Ishrat Naz; Ashfaq Ahmad Khan; Dima Semaan; Mohammad Rafiullah Khan (Natural Product Research, 2017)

Impact of Distribution Type in Bayes Probability Flood Forecasting - Wei Li; Jianzhong Zhou; Huaiwei Sun; Kuaile Feng; Hairong Zhang; Muhammad Tayyab (Water Resources Management, 2017)

Predicting Peak Flows in Real Time through Event Based Hydrologic Modeling for a Trans-Boundary River Catchment - Muhammad Adnan Shahid; Piero Boccardo; Muhammad Usman; Adriana Albanese; Muhammad Uzair Qamar (Water Resources Management, 2017)

Incorporation of estradiol benzoate to CIDR protocol improves the reproductive responses in crossbred dairy heifers - Muhammad Usman Mehmood; Ahmad Qamar; Abdul Sattar; Liaquat Ahmad; Nasim Ahmad (Tropical Animal Health and Production, 2017)

Arabidopsis AtNAP functions as a negative regulator via repression of AREB1 in salt stress response - Hye-Yeon Seok; Dong-Hyuk Woo; Linh Vu Nguyen; Huong T. Tran; Vaishali N. Tarte; Syed Muhammad Muntazir Mehdi; Sun-Young Lee; Yong-Hwan Moon (Planta, 2017)

Use of TALEs and TALEN Technology for Genetic Improvement of Plants - Zulqurnain Khan; Sultan Habibullah Khan; Muhammad Salman Mubarik; Bushra Sadia; Aftab Ahmad (Plant Molecular Biology Reporter, 2017)

Elevated carbon dioxide ameliorates the effect of Zn deficiency and terminal drought on wheat grain yield but compromises nutritional quality - Muhammad Asif; Ozlem Yilmaz; Levent Ozturk (Plant and Soil, 2017)

Toxicity of butene-fipronil, in comparison with seven other insecticides, in Leptinotarsa decemlineata and Drosophila melanogaster - Muhammad Shahid Arain; Pin-Jun Wan; Muhammad Shakeel; Muhammad Farooq; Xing-Xing Hu; Syed Ali Haider Shah; Muhammad Esmail Abdalla Elzaki; Guo-Qing Li (Phytoparasitica, 2017)

Effect of resveratrol and environmental enrichment on biomarkers of oxidative stress in young healthy mice - Mustapha Shehu Muhammad; Rabiu Abdussalam Magaji; Aliyu Mohammed; Ahmed-Sherif Isa; Mohammed Garba Magaji (Metabolic Brain Disease, 2017)

Endophytes from medicinal plants and their potential for producing indole acetic acid, improving seed germination and mitigating oxidative stress - Abdul Latif Khan; Syed Abdullah Gilani; Muhammad Waqas; Khadija Al-Hosni; Salima Al-Khiziri; Yoon-Ha Kim; Liaqat Ali; Sang-Mo Kang; Sajjad Asaf; Raheem Shahzad; Javid Hussain; In-Jung Lee; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Additive effects due to biochar and endophyte application enable soybean to enhance nutrient uptake and modulate nutritional parameters - Muhammad Waqas; Yoon-Ha Kim; Abdul Latif Khan; Raheem Shahzad; Sajjad Asaf; Muhammad Hamayun; Sang-Mo Kang; Muhammad Aaqil Khan; In-Jung Lee (Journal of Zhejiang University-SCIENCE B, 2017)

Congener-specific evaluation of biota-sediment accumulation factor model for HCHs and DDTs under small-scale in situ riverine condition - Muhammad Aamir; Sardar Khan; Mengling Tang; Zahir Qamar; Anwarzeb Khan; Javed Nawab (Journal of Soils and Sediments, 2017)

Segmented Loop Algorithm of Theoretical Calculation of Trajectory of Rockfall - Muhammad Irfan; Yulong Chen (Geotechnical and Geological Engineering, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Photosynthesis and growth response of maize (Zea mays L.) hybrids exposed to cadmium stress - Tasneem Akhtar; Muhammad Zia-ur-Rehman; Asif Naeem; Rab Nawaz; Shafaqat Ali; Ghulam Murtaza; Muhammad Aamer Maqsood; Muhammad Azhar; Hinnan Khalid; Muhammad Rizwan (Environmental Science and Pollution Research, 2017)

Equilibrium modeling of cadmium biosorption from aqueous solution by compost - Iftikhar Ahmad; Muhammad Javed Akhtar; Iram Bashir Khan Jadoon; Muhammad Imran; Muhammad Imran; Shahid Ali (Environmental Science and Pollution Research, 2017)

Microwave-assisted enhancement of milkweed (Calotropis procera L.) leaves as an eco-friendly source of natural colorants for textile - Muhammad Hussaan; Naeem Iqbal; Shahid Adeel; Muhammad Azeem; M. Tariq Javed; Ali Raza (Environmental Science and Pollution Research, 2017)

Health assessment using aqua-quality indicators of alpine streams (Khunjerab National Park), Gilgit, Pakistan - Salar Ali; Junfeng Gao; Farida Begum; Atta Rasool; Muhammad Ismail; Yongjiu Cai; Shaukat Ali; Shujaat Ali (Environmental Science and Pollution Research, 2017)

Production of α-1,4-glucosidase from Bacillus licheniformis KIBGE-IB4 by utilizing sweet potato peel - Muhammad Asif Nawaz; Zainab Bibi; Asad Karim; Haneef Ur Rehman; Muhsin Jamal; Tour Jan; Afsheen Aman; Shah Ali Ul Qader (Environmental Science and Pollution Research, 2017)

Low C/N ratio raw textile wastewater reduced labile C and enhanced organic-inorganic N and enzymatic activities in a semiarid alkaline soil - Mahnaz Roohi; Muhammad Riaz; Muhammad Saleem Arif; Sher Muhammad Shahzad; Tahira Yasmeen; Muhammad Arslan Ashraf; Muhammad Atif Riaz; Ishaq A. Mian (Environmental Science and Pollution Research, 2017)

Persistent organic pollutants (POPs): a global issue, a global challenge - Muhammad Aqeel Ashraf (Environmental Science and Pollution Research, 2017)

Plant–bacteria partnerships for the remediation of persistent organic pollutants - Muhammad Arslan; Asma Imran; Qaiser Mahmood Khan; Muhammad Afzal (Environmental Science and Pollution Research, 2017)

Spatio-statistical analysis of temperature fluctuation using Mann–Kendall and Sen’s slope approach - Atta-ur-Rahman; Muhammad Dawood (Climate Dynamics, 2017)

Chromium Exposure in the Adult Population, Consuming Different Types of Smokeless Tobacco Products in Pakistan - Asma Akhtar; Hasan Imran Afridi; Tasneem Gul Kazi; Farah Naz Talpur; Sadaf Sadia Arain; Jameel Ahmed Baig; Noman Khan; Mustafa Khan; Muhammad Bilal (Biological Trace Element Research, 2017)

Methane alleviates copper-induced seed germination inhibition and oxidative stress in Medicago sativa - Muhammad Kaleem Samma; Heng Zhou; Weiti Cui; Kaikai Zhu; Jing Zhang; Wenbiao Shen (BioMetals, 2017)

Transgenic expression of phytase in wheat endosperm increases bioavailability of iron and zinc in grains - Nabeela Abid; Asia Khatoon; Asma Maqbool; Muhammad Irfan; Aftab Bashir; Irsa Asif; Muhammad Shahid; Asma Saeed; Henrik Brinch-Pedersen; Kauser A. Malik (Transgenic Research, 2017)

Rock physics modelling in reservoirs within the context of time lapse seismic using well log data - Muhammad Toqeer; Aamir Ali (Geosciences Journal, 2017)

Evaluating the impact of classification algorithms and spatial resolution on the accuracy of land cover mapping in a mountain environment in Pakistan - Sami Ullah; Muhammad Shafique; Muhammad Farooq; Muhammad Zeeshan; Matthias Dees (Arabian Journal of Geosciences, 2017)

Unraveling the inheritance pattern of yield and associated traits in Rapeseed (Brassica napus L.) - Muhammad Ishaq; Sabaz Ali Khan; Raziuddin Razi (Acta Physiologiae Plantarum, 2017)

Epidemiology of Toxoplasma gondii infection in native Tibetans in Tibet, China - Kun Li; Meng Wang; Hui Zhang; Zhixin Lei; Lihong Zhang; Houqiang Luo; Gang Qiu; Khalid Mehmood; Muhammad Shahzad; Jiakui Li (Acta Parasitologica, 2017)
(

Biosynthesis and role of 3-methylbutanal in cheese by lactic acid bacteria: Major metabolic pathways, enzymes involved, and strategies for control - Muhammad Inam Afzal; Citlalli Celeste González Ariceaga; Kenza-Amel Boulahya; Muriel Jacquot; Stéphane Delaunay; Catherine Cailliez-Grimal (Critical Reviews in Food Science and Nutrition, 2017)

Prospective study of avian influenza H9 infection in commercial poultry farms of Punjab Province and Islamabad Capital Territory, Pakistan - Mamoona Chaudhry; Maqbool Ahmad; Hamad Bin Rashid; Bakhat Sultan; Haroon Rashid Chaudhry; Aayesha Riaz; Muhammad Shabir Shaheen (Tropical Animal Health and Production, 2017)

RETRACTED ARTICLE: Beta-cyanoalanine synthase pathway as a homeostatic mechanism for cyanide detoxification as well as growth and development in higher plants - Hafiz Mamoon Rehman; Zahid Hussain Shah; Muhammad Amjad Nawaz; Muhammad Qadir Ahmad; Seung Hwan Yang; Kang Hee Kho; Gyuhwa Chung (Planta, 2017)

Differences in photosynthetic syndromes of four halophytic marsh grasses in Pakistan - Muhammad Moinuddin; Salman Gulzar; Abdul Hameed; Bilquees Gul; M. Ajmal Khan; Gerald E. Edwards (Photosynthesis Research, 2017)

Organic Material Based Fluorescent Sensor for Hg2+: a Brief Review on Recent Development - Muhammad Saleem; Muhammad Rafiq; Muhammad Hanif (Journal of Fluorescence, 2017)

Erratum to: Cost-effective enhanced iron bioavailability in rice grain grown on calcareous soil by sulfur mediation and its effect on heavy metals mineralization - Pia Muhammad Adnan Ramzani; Muhammad Khalid; Shazia Anjum; Waqas-ud-Din Khan; Shafaqat Ali; Fakhir Hannan; Muhammad Iqbal (Environmental Science and Pollution Research, 2017)

Investigating the nitrogen dioxide concentrations in the boundary layer by using multi-axis spectroscopic measurements and comparison with satellite observations - Muhammad Fahim Khokhar; Munazza Nisar; Asma Noreen; Waseem Razzaq Khan; Khalid Rehman Hakeem (Environmental Science and Pollution Research, 2017)

The knowledge, awareness, attitude and motivational analysis of plastic waste and household perspective in Malaysia - Rafia Afroz; Ataur Rahman; Muhammad Mehedi Masud; Rulia Akhtar (Environmental Science and Pollution Research, 2017)

Cost-effective enhanced iron bioavailability in rice grain grown on calcareous soil by sulfur mediation and its effect on heavy metals mineralization - Pia Muhammad Adnan Ramzani; Muhammad Khalid; Shazia Anjum; Waqas-ud-Din Khan; Shafaqat Ali; Fakhir Hannan; Muhammad Iqbal (Environmental Science and Pollution Research, 2017)

Nitrogen fertilization and conservation tillage: a review on growth, yield, and greenhouse gas emissions in cotton - Adnan Noor Shah; Javaid Iqbal; Mohsin Tanveer; Guozheng Yang; Waseem Hassan; Shah Fahad; Muhammad Yousaf; Yingying Wu (Environmental Science and Pollution Research, 2017)

The occurrence and potential ecological risk assessment of bauxite mine-impacted water and sediments in Kuantan, Pahang,Malaysia - Faradiella Mohd Kusin; Muhammad Syazwan Abd Rahman; Zafira Madzin; Shamshuddin Jusop; Ferdaus Mohamat-Yusuff; Mariani Ariffin; Mohd Syakirin Md Z (Environmental Science and Pollution Research, 2017)

Health risk assessment of heavy metals in wheat using different water qualities: implication for human health - Zafar Iqbal Khan; Kafeel Ahmad; Sidrah Rehman; Samra Siddique; Humayun Bashir; Asma Zafar; Muhammad Sohail; Salem Alhajj Ali; Eugenio Cazzato; Giuseppe De Mastro (Environmental Science and Pollution Research, 2017)

Historical and projected changes in the Southern Hemisphere Sub-tropical Jet during winter from the CMIP5 models - Sheeba Nettukandy Chenoli; Muhammad Yunus Ahmad Mazuki; John Turner; Azizan Abu Samah (Climate Dynamics, 2017)

Rutin Attenuates Carfilzomib-Induced Cardiotoxicity Through Inhibition of NF-κB, Hypertrophic Gene Expression and Oxidative Stress - Faisal Imam; Naif O. Al-Harbi; Mohammed M. Al-Harbia; Hesham M. Korashy; Mushtaq Ahmad Ansari; Mohamed M. Sayed-Ahmed; Mahmoud N. Nagi; Muzaffar Iqbal; Md. Khalid Anwer; Imran Kazmi; Muhammad Afzal; Saleh Bahashwan (Cardiovascular Toxicology, 2017)

Determination of Serum Trace Elements (Zn, Cu, and Fe) in Pakistani Patients with Rheumatoid Arthritis - Zia Ullah; Muhammad Ikram Ullah; Shabbir Hussain; Haiba Kaul; Khalid P. Lone (Biological Trace Element Research, 2017)

Applications of variogram modeling to electrical resistivity data for the occurrence and distribution of saline groundwater in Domail Plain, northwestern Himalayan fold and thrust belt, Pakistan - Asam Farid; Perviez Khalid; Klian Zaib Jadoon; Muhammad Asim Iqbal; Muhammad Shafique (Journal of Mountain Science, 2017)

Mix cropping of legume (Vigna Radiata) and non-legume (Zea Mays) crops alleviates water stress as revealed by growth and biochemical parameters - Kalim Ullah Khan; Waheed Murad; Azizullah Azizullah; Hazir Rahman; Muhammad Daud Khan (Acta Physiologiae Plantarum, 2017)

Chitosan alleviates phytotoxicity caused by boron through augmented polyamine metabolism and antioxidant activities and reduced boron concentration in Cucumis sativus L. - Rashad Mukhtar Balal; Muhammad Adnan Shahid; Muhammad Mansoor Javaid; Zafar Iqbal; Guodong David Liu; Lincoln Zotarelli; Naeem Khan (Acta Physiologiae Plantarum, 2017)

Enhancement of phenolic compounds production in in vitro grown Rumex cyprius Murb. - Wesam Al Khateeb; Muhammad Alu’datt; Haifa Al Zghoul; Razan Kanaan; Ahmad El-Oqlah; Jamil Lahham (Acta Physiologiae Plantarum, 2017)

Prevalence of three Oesophagostomum spp. from Tibetan Pigs analyzed by Genetic Markers of nad1, cox3 and ITS1 - Kun Li; Yanfang Lan; Houqiang Luo; Muhammad Shahzad; Hui Zhang; Lei Wang; Lihong Zhang; Dongyu Liu; Xinyu Liu; Yanan Hao; Suolang Sizhu; Jiakui Li (Acta Parasitologica, 2017)
Parasitic nematodes of